Resin composition
A resin composition with an oligophenylene ether skeleton and inorganic filler addresses the trade-off between dielectric properties and warpage, ensuring robust mechanical strength and low transmission loss in semiconductor packaging.
Patent Information
- Application Number
- CN202410784607.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-20
- Filing Date
- 2024-06-18
- Publication Date
- 2024-12-20
AI Technical Summary
Existing resin compositions face a trade-off between low dielectric loss tangent and warpage reduction, especially in large-scale semiconductor packaging, and suffer from reduced mechanical strength under high temperature and humidity conditions.
A resin composition comprising a thermosetting resin, inorganic filler, and a resin with an oligophenylene ether skeleton having a glass transition temperature of 25°C or less, achieving a bolt pull-off adhesion strength of 600 kgf/cm², which suppresses warping and maintains good dielectric properties and mechanical strength.
The composition effectively reduces warpage and transmission loss in high-frequency environments while maintaining mechanical strength under high temperature and humidity, enhancing the reliability of semiconductor packaging.
Smart Images

Figure BDA0004898248410000091 
Figure BDA0004898248410000101 
Figure BDA0004898248410000111
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and further to a resin sheet, a semiconductor chip package, a circuit substrate and a semiconductor device. Background Art
[0002] The development of next-generation high-speed communications has further increased the need for low dielectric loss tangent for insulating materials such as sealing materials for semiconductor chip packaging and interlayer insulating materials for circuit substrates. Furthermore, with the demand for larger substrates such as wafer-level packaging (WLP) and panel-level packaging (PLP), it has become more important to reduce warpage in the overall package structure.
[0003] Conventionally, excellent dielectric properties have been ensured by adding a high amount of inorganic fillers or stress relaxation agents, and low warpage has been achieved by utilizing low thermal expansion and stress relaxation capabilities (eg, Patent Document 1).
[0004] Prior art literature Patent Document 1: Japanese Patent Application Publication No. 2018-168217
[0005] Technical problem to be solved by the invention On the other hand, it is known that when a lower warpage is required due to the demand for larger size, more stress relaxants need to be added, but a trade-off with low dielectric loss tangent must be considered. Furthermore, if a large amount of stress relaxants with a low glass transition temperature are added, there is a problem of reduced resin strength when exposed to high temperature and high humidity environments such as reliability tests (HAST).
[0006] An object of the present invention is to provide a resin composition that can provide a cured product that can suppress warping, exhibits good dielectric properties, and maintains good mechanical strength even when exposed to a high-temperature, high-humidity environment.
[0007] Means of solving technical problems The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by a resin composition having the following structure, which includes a resin containing a specific oligophenylene ether skeleton (hereinafter also referred to as "resin containing an oligophenylene ether skeleton") and has a bolt pull-off adhesion strength within a specific range after curing, thereby completing the present invention.
[0008] That is, the present invention includes the following contents. [1] A resin composition comprising a thermosetting resin, an inorganic filler and a resin X having an oligophenylene ether skeleton and having a glass transition temperature of 25° C. or less; The cured product of the resin composition has a bolt pull adhesion strength of 600 kgf / cm 2 above. [2] The resin composition according to [1], wherein the content of the resin X is 10% by mass or more and less than 60% by mass, based on 100% by mass of the resin component in the resin composition. [3] The resin composition according to [1] or [2], wherein the content of the inorganic filler is 50% by mass or more when the non-volatile component in the resin composition is 100% by mass. [4] The resin composition according to any one of [1] to [3], wherein the resin X comprises one or more structural units selected from the group consisting of polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic acid structural units, and polysiloxane structural units. [5] The resin composition according to any one of [1] to [4], wherein the resin X contains a cyclic imide structure. [6] The resin composition according to any one of [1] to [5], which is used for semiconductor sealing. [7] The resin composition according to any one of [1] to [5], which is used for an insulating layer of a circuit board. [8] A cured product of the resin composition according to any one of [1] to [7]. [9] A resin sheet comprising a support and a layer of the resin composition according to any one of [1] to [7] provided on the support.
[10] The resin sheet according to [9], wherein the support is a thermoplastic resin film or a metal foil.
[11] A semiconductor chip package comprising a sealing layer formed from a cured product of the resin composition according to any one of [1] to [6].
[12] A circuit board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to [5] and [7].
[13] A semiconductor device comprising the semiconductor chip package described in
[11] .
[14] A semiconductor device comprising the circuit substrate described in
[12] .
[0009] Effects of the Invention According to the present invention, there can be provided a novel resin composition which can suppress warping, exhibit good dielectric properties, and produce a cured product which maintains good mechanical strength even when exposed to a high temperature and high humidity environment. DETAILED DESCRIPTION
[0010] <Explanation of terms> In the present specification, the term "optionally having a substituent" with respect to a compound or a group refers to both the case where hydrogen atoms of the compound or group are not substituted by a substituent and the case where part or all of the hydrogen atoms of the compound or group are substituted by a substituent.
[0011] In the present specification, the term "substituent" means a halogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an alkoxy group, a cycloalkyloxy group, an aryl group, an aryloxy group, an aralkyl group, an arylalkoxy group, a monovalent heterocyclic group, an alkylidene group, an amino group, a silyl group, a carboxyl group, a sulfo group, a cyano group, a nitro group, a hydroxyl group, a mercapto group, and an oxo group, unless otherwise specified.
[0012] As the halogen atom used as a substituent, for example, a fluorine atom, a chlorine atom, a bromine atom and an iodine atom can be mentioned. The alkyl group used as a substituent may be either linear or branched. The number of carbon atoms of the alkyl group is preferably 1 to 12, more preferably 1 to 6, and further preferably 1 to 3. The alkenyl group used as a substituent may be either linear or branched. The number of carbon atoms of the alkenyl group is preferably 2 to 12, more preferably 2 to 6, and further preferably 2 or 3. The number of carbon atoms of the cycloalkyl group used as a substituent is preferably 3 to 12, and further preferably 3 to 6. The alkoxy group used as a substituent may be either linear or branched. The number of carbon atoms of the alkoxy group is preferably 1 to 12, and further preferably 1 to 6. The number of carbon atoms of the cycloalkoxy group used as a substituent is preferably 3 to 12, and further preferably 3 to 6. The aryl group used as a substituent is a group obtained by removing one hydrogen atom from an aromatic ring of an aromatic hydrocarbon. The number of carbon atoms of the aryl group used as a substituent is preferably 6 to 14, and further preferably 6 to 10. The number of carbon atoms of the aryloxy group used as a substituent is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms of the aralkyl group used as a substituent is preferably 7 to 15, more preferably 7 to 11. The number of carbon atoms of the arylalkoxy group used as a substituent is preferably 7 to 15, more preferably 7 to 11. The monovalent heterocyclic group used as a substituent refers to a group obtained by removing one hydrogen atom from the heterocyclic ring of a heterocyclic compound. The number of carbon atoms of the monovalent heterocyclic group is preferably 3 to 15, more preferably 3 to 9. The alkylidene group used as a substituent refers to a group obtained by removing two hydrogen atoms from the same carbon atom of an alkane. The number of carbon atoms of the alkylidene group is preferably 1 to 12, more preferably 1 to 6, and even more preferably 1 to 3. The above-mentioned substituent may further have a substituent (hereinafter sometimes referred to as a "secondary substituent"). As the secondary substituent, the same group as the above-mentioned substituent may be used unless otherwise specified.
[0013] Hereinafter, the present invention will be described in detail with reference to the embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and can be implemented with any modifications within the scope of the claims and their equivalents.
[0014] [Resin composition] The resin composition of the present invention is characterized in that the resin composition comprises Thermosetting resin, Inorganic fillers, and A resin X containing an oligophenylene ether skeleton having a glass transition temperature of 25°C or less, The bolt pull-off strength of the resin composition is 600 kgf / cm 2 above.
[0015] As mentioned above, in recent years, insulating materials such as sealing materials for semiconductor chip packages and interlayer insulating materials for circuit substrates are required to have low dielectric loss tangent in order to reduce transmission loss when operating in high-frequency environments for next-generation high-speed communications. In addition, as substrates such as WLP and PLP are required to be larger, it is becoming more important to reduce warpage in the overall package structure. In response to such requirements, in the past, excellent dielectric properties were ensured by high-mixing inorganic fillers or stress relaxants, while low thermal expansion and stress relaxation capabilities were used to achieve low warpage. However, it is known that when lower warpage is required as the demand for large-scale production increases, more stress relaxants need to be added, but this must be balanced with the low dielectric loss tangent. Furthermore, if a large amount of stress relaxants with a low glass transition temperature are added, there is also a problem of reduced resin strength when exposed to high temperature and high humidity environments such as reliability tests (HAST).
[0016] On the other hand, the resin composition according to the present invention comprises a resin X having an oligophenylene ether skeleton and a glass transition temperature of 25° C. or less in combination with a thermosetting resin and an inorganic filler, and exhibits a thermal conductivity of 600 kgf / cm 2 The above bolt pull-on close strength can produce a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength when exposed to a high temperature and high humidity environment. In this way, the resin composition of the present invention can advantageously reduce the transmission loss when working in a high frequency environment required in the next generation of high-speed communications, and at the same time, it has a significant contribution to the realization of low-warping and high-reliability insulating materials.
[0017] Hereinafter, each component will be described.
[0018] <Thermosetting resin> The resin composition of the present invention contains a thermosetting resin.
[0019] The thermosetting resin is not particularly limited, and examples thereof include epoxy resins, benzocyclobutene resins, epoxy acrylate resins, urethane acrylate resins, polyurethane resins, cyanate resins, polyimide resins, benzoxazine resins, unsaturated polyester resins, melamine resins, silicone resins, etc. Among them, in combination with the inorganic filler and the resin X containing an oligophenylene ether skeleton described later, it is preferred to include an epoxy resin from the viewpoint of providing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment.
[0020] As long as epoxy resin has more than one (preferably more than 2) epoxy groups in 1 molecule, its kind is not particularly limited. As epoxy resin, for example, bisphenol type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin with butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, epoxy resin containing spiro ring, cyclohexane type epoxy resin, cyclohexanedimethanol type epoxy resin, naphthyl ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin can be enumerated. Bisphenol epoxy resin refers to epoxy resin having a bisphenol structure, and examples thereof include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, and bisphenol AF epoxy resin. Biphenyl epoxy resin refers to epoxy resin having a biphenyl structure, and the biphenyl structure may optionally have a substituent such as an alkyl group, an alkoxy group, or an aryl group. Therefore, biphenyl epoxy resin and biphenyl aralkyl epoxy resin are also included in biphenyl epoxy resin.
[0021] Epoxy resins can be divided into epoxy resins that are liquid at a temperature of 20°C (hereinafter referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter referred to as "solid epoxy resins"). The resin composition of the present invention may contain only liquid epoxy resins, only solid epoxy resins, or a combination of liquid epoxy resins and solid epoxy resins.
[0022] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.
[0023] As the liquid epoxy resin, preferred are GLYCIROL type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexanedimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure.
[0024] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX, "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", "HP4032SS" manufactured by DIC Corporation (naphthalene-type epoxy resins); "828US", "828EL", "825" (bisphenol A-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807", "1750" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "HP4032" (naphthalene-type epoxy resin) manufactured by DIC Corporation. "630", "630LSD", "604" (glycidylamine type epoxy resin) made by ADEKA; "ED-523T" (GLYCIROL type epoxy resin) made by ADEKA; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) made by ADEKA; "EP-4088S" (dicyclopentadiene type epoxy resin) made by ADEKA; "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) made by Nippon Steel Chemical Materials Co., Ltd.; Nagase "EX-721" (glycidyl ester type epoxy resin) manufactured by ChemteX; "EX-991L" (epoxy resin containing an alkylene oxide skeleton and a butadiene skeleton) manufactured by Nagase ChemteX; "CELLOXIDE 2021P" (alicyclic epoxy resin with an ester skeleton) manufactured by Daicel; "PB-3600" manufactured by Daicel, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins with a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "EG-280" (epoxy resin containing a fluorene structure) manufactured by Osaka Gas Chemical Co., Ltd.; "EX-201" (cyclic aliphatic glycidyl ether) manufactured by Nagase ChemteX, etc.
[0025] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferred.
[0026] As the solid epoxy resin, preferred are biphenylol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, naphthol novolac type epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthyl ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, phenol aralkyl type epoxy resin, tetraphenylethane type epoxy resin, and phenolphthalimidine type epoxy resin.
[0027] Specific examples of solid epoxy resins include "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation; and "HP-7200HH" and "HP-7200H" and "HP-7200L" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation. "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP-6000", "HP-6000L" (naphthyl ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. Resin); "ESN475V", "ESN4100V" (naphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "YX4000H", "YX4000", "YX4000HK", "YL7890" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Resin); "YX7700" (phenol aralkyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "WHR991S" (phenol benzopyrrolone type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., etc. These can be used alone or in combination of two or more.
[0028] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, their mass ratio (liquid epoxy resin:solid epoxy resin) is preferably 10:1 to 1:50, more preferably 5:1 to 1:20, further preferably 2:1 to 1:10, and particularly preferably 1:1 to 1:3.
[0029] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., further preferably 70 g / eq. to 1,000 g / eq., and further more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per 1 equivalent of epoxy group. The epoxy equivalent can be measured according to JIS K7236.
[0030] The weight average molecular weight of the epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500. The weight average molecular weight of the resin can be measured as a value in terms of polystyrene by gel permeation chromatography (GPC).
[0031] The content of the thermosetting resin in the resin composition is not particularly limited. When the resin component in the resin composition is set to 100% by mass, it is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 12% by mass or more, 14% by mass or more, or 15% by mass or more. The upper limit of this content is not particularly limited, and can be determined according to the desired characteristics of the resin composition, for example, it can be 60% by mass or less, 50% by mass or less, or 40% by mass or less.
[0032] In the present invention, the "resin component" referred to in the resin composition refers to a component obtained by removing the above-mentioned inorganic filler from the non-volatile components constituting the resin composition.
[0033] <Inorganic filler> The resin composition of the present invention contains an inorganic filler. By containing an inorganic filler, the thermal expansion coefficient and the dielectric loss tangent can be reduced.
[0034] As inorganic filler, for example, silicon dioxide, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum silicate, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate, etc. can be cited. Among them, silicon dioxide is particularly preferred. As silicon dioxide, for example, amorphous silicon dioxide, fused silica, crystalline silicon dioxide, synthetic silicon dioxide, hollow silica, etc. can be cited. In addition, as silicon dioxide, spherical silicon dioxide is preferred. Inorganic filler can be used alone or in combination of two or more.
[0035] Commercially available inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama; and "CellSpheres" and "MGH-005" manufactured by Pacific Cement Co., Ltd.
[0036] The average particle size of the inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, 2 μm or less, 1 μm or less, or 0.7 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.07 μm or more, 0.1 μm or more, or 0.2 μm or more. The average particle size of the inorganic filler can be measured by the laser diffraction / scattering method based on Mie scattering theory. Specifically, the particle size distribution of the inorganic filler can be made on a volume basis by a laser diffraction scattering particle size distribution measuring device, and the median diameter thereof is measured as the average particle size. The sample can be measured using 100 mg of inorganic filler and 10 g of methyl ethyl ketone weighed into a vial and dispersed with ultrasound for 10 minutes. For the sample, a laser diffraction particle size distribution measuring device is used, and the wavelength of the light source is set to blue and red, and the particle size distribution of the volume basis of the inorganic filler is measured in a flow cell mode, and the average particle size is calculated as the median particle size according to the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba, Ltd. can be cited.
[0037] The specific surface area of the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, 3m 2 / g or above or 5m 2 The upper limit of the specific surface area is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 80m 2 / g or less, more preferably 60m 2 / g or less, 50m 2 / g or below or 40m 2 / g or less. The specific surface area of the inorganic filler can be obtained by adsorbing nitrogen gas on the sample surface using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0038] The inorganic filler is preferably surface treated with an appropriate surface treatment agent. By performing surface treatment, the moisture resistance and dispersibility of the inorganic filler can be improved. As the surface treatment agent, for example, vinyl silane coupling agent, epoxy silane coupling agent, styrene silane coupling agent, (meth) acrylic silane coupling agent, amino silane coupling agent, isocyanurate silane coupling agent, urea silane coupling agent, mercapto silane coupling agent, isocyanate silane coupling agent, anhydride silane coupling agent and other silane coupling agents; non-silane coupling-alkoxysilane compounds such as methyltrimethoxysilane and phenyltrimethoxysilane; silazane compounds, etc. The surface treatment agent can be used alone or in combination of two or more.
[0039] Commercially available products of the surface treatment agent include, for example, “KBM403” (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM803” (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBE903” (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM573” (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., and “SZ-31” (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0040] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment by the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface treated with 0.2 to 5% by mass of the surface treatment agent.
[0041] The degree of surface treatment by the surface treatment agent can be evaluated by the carbon content per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the carbon content per unit surface area of the inorganic filler is preferably 0.02 mg / m 2 More preferably 0.1 mg / m 2 More preferably, 0.2 mg / m 2 On the other hand, from the viewpoint of preventing the melt viscosity of the resin composition or the melt viscosity of the sheet form from increasing, 1.0 mg / m 2 Below, more preferably 0.8 mg / m2 Below, more preferably 0.5 mg / m 2 Below. The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is cleaned with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK can be added as a solvent to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid components, the amount of carbon per unit surface area of the inorganic filler is measured using a carbon analyzer. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd., etc. can be used.
[0042] From the viewpoint of bringing a cured product that can suppress warping, present good dielectric properties, and can also maintain good mechanical strength when exposed to a high temperature and high humidity environment, the content of the inorganic filler in the resin combination, when the non-volatile component in the resin combination is set to 100 mass %, is preferably more than 50 mass %, more preferably more than 55 mass %, and more preferably more than 60 mass %. According to the present invention of the resin X containing an oligophenylene ether skeleton described later, it is possible to achieve good low warpage and high reliability after exposure to a high temperature and high humidity environment, while the content of the inorganic filler can be further improved. For example, when the non-volatile component in the resin combination is set to 100 mass %, the content of the inorganic filler in the resin combination can be increased to more than 62 mass %, more than 64 mass %, more than 65 mass %, more than 66 mass % or more than 68 mass %. The upper limit of the content of the inorganic filler is not particularly limited, for example, can be less than 90 mass %, less than 85 mass %, etc.
[0043] <Resin X containing an oligophenylene ether skeleton> The resin composition of the present invention contains a resin X having an oligophenylene ether skeleton and having a glass transition temperature of 25° C. or less (also simply referred to as “resin X”). Here, the glass transition temperature of the resin X being 25° C. or lower means that if the resin X has only one glass transition temperature, the glass transition temperature is 25° C. or lower, and when the resin X has multiple glass transition temperatures, at least one glass transition temperature is 25° C. or lower. By using such a resin X in combination with a thermosetting resin and an inorganic filler, a resin composition can be realized that can suppress warping, exhibit good dielectric properties, and provide a cured product that maintains good mechanical strength even when exposed to a high temperature and high humidity environment.
[0044] -Oligophenyl ether skeleton- The resin X preferably includes an oligophenylene ether skeleton containing a plurality of phenylene ether units represented by the following formula (1).
[0045] [Chemical formula 1] (In formula (1), R each independently represents a halogen atom, an alkyl group optionally having a substituent, an alkoxy group optionally having a substituent, an aryl group optionally having a substituent, an amino group optionally having a substituent, a nitro group or a carboxyl group, m represents an integer from 0 to 4. )
[0046] The alkyl group or alkoxy group in R may be linear or branched, and the number of carbon atoms thereof is preferably 1 to 10, more preferably 1 to 6, and further preferably 1 to 4 or 1 to 3. The number of carbon atoms does not include the number of carbon atoms of the substituent.
[0047] The number of carbon atoms of the aryl group in R is preferably 6 to 14, more preferably 6 to 10. This number of carbon atoms does not include the number of carbon atoms of the substituent.
[0048] The substituents that the monovalent group represented by R may have are as described above, and are preferably at least one selected from a halogen atom, an alkyl group, an alkoxy group, and an aryl group, more preferably at least one selected from a halogen atom, an alkyl group, and an aryl group, and further preferably at least one selected from a fluorine atom, an alkyl group having 1 to 6 carbon atoms, and an aryl group having 6 to 10 carbon atoms.
[0049] In formula (1), m represents an integer of 0 to 4, preferably an integer of 0 to 3, and more preferably an integer of 1 to 3.
[0050] In combination with a thermosetting resin and an inorganic filler material, from the viewpoint of producing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment, the oligophenylene ether skeleton is preferably an oligophenylene ether skeleton comprising a plurality of at least one phenylene ether units selected from 2,6-disubstituted-1,4-phenylene ether units, 2,5-disubstituted-1,4-phenylene ether units, and 2,3,6-trisubstituted-1,4-phenylene ether units, among which an oligophenylene ether skeleton comprising a plurality of 2,6-disubstituted-1,4-phenylene ether units is preferred; wherein the substituents at the 2,6 positions, the substituents at the 2,5 positions, and the substituents at the 2,3,6 positions correspond to R in formula (1).
[0051] Specific examples of suitable oligophenylene ether skeletons include oligo(2,6-dialkyl-1,4-phenylene ether) skeletons, oligo(2-alkyl-6-aryl-1,4-phenylene ether) skeletons, oligo(2,6-diaryl-1,4-phenylene ether) skeletons, oligo(2,6-dihalogenated-1,4-phenylene ether) skeletons, and oligo(2,6-disubstituted-1,4-phenylene ether) skeletons; oligo(2,6-disubstituted phenol) skeletons and other phenol compounds (e.g., 2 The present invention relates to an oligophenyl ether skeleton comprising a plurality of 2,6-disubstituted-1,4-phenyl ether units, such as a skeleton formed by a copolymerization structure of 2,5-disubstituted phenols such as 2,5-dialkylphenol, 2-alkyl-5-arylphenol, and 2,5-diarylphenol, or a 2,3,6-trisubstituted phenol such as 2,3,6-trialkylphenol and 2,3,6-trihalogenated phenol, or a coupling reaction product of 2,6-disubstituted phenol and a biphenol compound or a bisphenol compound.
[0052] In combination with a thermosetting resin and an inorganic filler, the resin X preferably contains a structure represented by the following formula (2) as an oligophenylene ether skeleton from the viewpoint of providing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment.
[0053] [Chemical formula 2] (In formula (2), R and m have the same meanings as above. L represents a divalent linking group, n1 and n2 each independently represent an integer of 1 to 100.)
[0054] In formula (2), L represents a divalent linking group. Examples of the divalent linking group include a single bond, an alkylene group optionally having a substituent, an alkenylene group optionally having a substituent, an arylene group optionally having a substituent, an alkylarylene group optionally having a substituent, a heteroarylene group optionally having a substituent, -O-, -NH-, -NR- x -, -CO-, -CS-, -SO-, -SO2-, -C(=O)O-, -NHC(=O)-, -NC(=O)N-, NHC(=O)O-, -C(=O)-, -S-, and a divalent group formed by combining a plurality of these groups. x It represents a hydrocarbon group having 1 to 12 carbon atoms.
[0055] Among them, from the viewpoint of enjoying the effects of the present invention more, the divalent linking group represented by L is preferably a single bond, an alkylene group optionally having a substituent, an alkenylene group optionally having a substituent, an arylene group optionally having a substituent, -O-, -NR x-, -CO-, -CS-, -SO-, -SO2-, and a divalent group formed by combining a plurality of these groups, more preferably a single bond, an alkylene group optionally having a substituent, an arylene group optionally having a substituent, and a divalent group formed by combining a plurality of these groups.
[0056] The substituents that the divalent group in L may have are as described above, but from the viewpoint of being able to better enjoy the effects of the present invention, they are preferably at least one selected from halogen atoms and hydrocarbon groups, more preferably at least one selected from halogen atoms, alkyl groups and aryl groups, and further preferably at least one selected from fluorine atoms, alkyl groups having 1 to 6 carbon atoms and aryl groups having 6 to 10 carbon atoms.
[0057] The number of carbon atoms of the divalent linking group represented by L is preferably 60 or less, more preferably 48 or less, further preferably 36 or less, and further more preferably 24 or less.
[0058] Among them, in combination with a thermosetting resin and an inorganic filler, from the viewpoint of providing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment, the divalent linking group represented by L is preferably an alkylene group having 1 to 6 carbon atoms, or a divalent group represented by the following formula (3).
[0059] [Chemical formula 3] (In formula (3), R 1 To R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group, * indicates a chemical bond. )
[0060] In formula (3), R 1 To R 8 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group. 1 , R 2 , R 7 and R 8 Preferably, it is an alkyl group having 1 to 6 carbon atoms, and more preferably, it is an alkyl group having 1 to 4 carbon atoms. 3 and R 4 One of them represents a hydrogen atom, and the other represents an alkyl group having 1 to 6 carbon atoms, preferably R 5 and R 6 One of them represents a hydrogen atom, and the other represents an alkyl group having 1 to 6 carbon atoms.
[0061] In formula (2), R and m are as described above for the phenylene ether unit of formula (1). From the viewpoint of being able to enjoy the effects of the present invention more, the phenylene ether unit constituting the oligophenylene ether skeleton represented by formula (2) is preferably a 2,6-disubstituted-1,4-phenylene ether unit, more preferably a 2,6-dialkyl-1,4-phenylene ether unit, a 2-alkyl-6-aryl-1,4-phenylene ether unit, a 2,6-diaryl-1,4-phenylene ether unit, or a 2,6-dihalogenated-1,4-phenylene ether unit.
[0062] In combination with a thermosetting resin and an inorganic filler, the resin X preferably contains a structure represented by the following formula (2-1) as an oligophenylene ether skeleton from the viewpoint of producing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment.
[0063] [Chemical formula 4] (In formula (2-1), R, L, n1 and n2 have the same meanings as above.)
[0064] In formula (2-1), R, L, n1 and n2 have the same meanings as above, and preferred examples thereof are also as described above. Among them, from the viewpoint of being able to further enjoy the effects of the present invention, R each independently represents preferably a halogen atom, an alkyl group or an aryl group, more preferably a halogen atom, an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and further preferably an alkyl group having 1 to 6 carbon atoms; L is preferably a single bond, an alkylene group which may have a substituent, an alkenylene group which may have a substituent, an arylene group which may have a substituent, -O-, -NR x -, -CO-, -CS-, -SO-, -SO2-, and a divalent group formed by combining multiple thereof, more preferably a single bond, an alkylene group optionally having a substituent, an arylene group optionally having a substituent, and a divalent group formed by combining multiple thereof, further preferably an alkylene group having 1 to 6 carbon atoms or a divalent group represented by the above formula (3); n1 and n2 each independently represent an integer in the range of 1 to 100, and in relation to the flexible skeleton described later, preferably represent an integer satisfying a range in which at least one glass transition temperature of the resin X is 25° C. or less, more preferably satisfying a preferred condition (the condition will be described later), and further preferably satisfying a range in which a preferred condition for the weight average molecular weight of the resin X is satisfied (the condition will be described later).
[0065] -Flexible skeleton- The resin X includes, in addition to the oligophenylene ether skeleton which is a rigid skeleton, a skeleton which is softer than the oligophenylene ether skeleton (also simply referred to as a "flexible skeleton").
[0066] In combination with a thermosetting resin and an inorganic filler, the resin X preferably contains one or more structural units selected from the group consisting of a polyolefin structural unit, a polycarbonate structural unit, a polyether structural unit, a polyester structural unit, a poly(meth)acrylic acid structural unit, and a polysiloxane structural unit as a flexible skeleton from the viewpoint of providing a cured product that can further suppress warping, exhibit better dielectric properties, and better maintain mechanical strength even when exposed to a high temperature and high humidity environment.
[0067] Examples of the polyolefin structural unit include polyethylene structural units, polypropylene structural units, polybutadiene structural units, hydrogenated polybutadiene structural units, polyisoprene structural units, and hydrogenated polyisoprene structural units. Here, the "hydrogenated polybutadiene structural unit" refers to a unit obtained by hydrogenating a part or all of the unsaturated bonds of the polybutadiene structural unit, and similarly, the "hydrogenated polyisoprene structural unit" refers to a unit obtained by hydrogenating a part or all of the unsaturated bonds of the polyisoprene structural unit.
[0068] For example, when the resin X is produced using a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polyolefin structure) as described later, the polyolefin structural unit may be a structural unit remaining after two or more hydroxyl groups are removed from the polyol compound containing a polyolefin structure. Commercially available products may be used for the polyol compound containing a polyolefin structure, and examples of such commercial products include "G-1000", "G-2000", "G-3000" (polybutadiene containing hydroxyl groups at both ends), "GI-1000", "GI-2000", "GI-3000" (hydrogenated polybutadiene containing hydroxyl groups at both ends) manufactured by Nippon Soda Co., Ltd.
[0069] Examples of the polycarbonate structural unit include aliphatic polycarbonates (polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, polycyclohexyl carbonate, etc.) and aromatic polycarbonates (polybisphenol A carbonate, polybisphenol F carbonate, polybisphenol S carbonate, etc.).
[0070] For example, when the resin X is produced using a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polycarbonate structure) as described later, the polycarbonate structural unit may be a structural unit remaining after removing two or more hydroxyl groups from the polyol compound containing a polycarbonate structure. The polyol compound containing a polycarbonate structure may be a commercially available product, and examples of the commercially available product include "T6002" and "T6001" (polycarbonates containing hydroxyl groups at both ends) manufactured by Asahi Kasei Corporation, and "C-1090", "C-2015N", "C-2090", and "C-3090" (polycarbonates containing hydroxyl groups at both ends) manufactured by Kuraray Co., Ltd.
[0071] Examples of the polyether structural unit include a polyethylene glycol structural unit, a polypropylene glycol structural unit, a polytetramethylene glycol structural unit, and a polybutylene glycol structural unit.
[0072] For example, when the resin X is produced using a polyol compound having a flexible skeleton (a polyol compound containing a polyether structure in this embodiment) as described below, the polyether structural unit may be a structural unit remaining after removing two or more hydroxyl groups from the polyol compound containing a polyether structure. As the polyol compound containing a polyether structure, commercially available products can be used. Examples of the commercially available products include "PLONON #102", "PLONON #104", "PLONON #201", "PLONON #202B", "PLONON #204", "PLONON #208", "UNILUBE 70DP-600B", and "UNILUBE 70DP-950B" (polyethylene glycol-polypropylene glycol copolymers) manufactured by NOF Corporation, and "Pluronic (registered trademark) L-23", "Pluronic L-31", "Pluronic L-44", "Pluronic L-61", "ADEKA Pluronic L-62", "Pluronic L-64", "Pluronic L-71", "Pluronic L-72", "Pluronic L-101", "Pluronic L-121", "Pluronic P-84", "Pluronic P-85", and "Pluronic P-86" manufactured by ADEKA Corporation. P-103", "Pluronic F-68", "Pluronic F-88", "Pluronic F-108", "Pluronic 25R-1", "Pluronic 25R-2", "Pluronic 17R-2", "Pluronic 17R-3", "Pluronic 17R-4" (polyethylene glycol-polypropylene glycol copolymer).
[0073] Examples of the polyester structural unit include a polyethylene terephthalate structural unit, a polybutylene terephthalate structural unit, a polyethylene naphthalate structural unit, a polybutylene naphthalate structural unit, and a polytrimethylene terephthalate structural unit.
[0074] For example, when the resin X is produced using a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polyester structure) as described later, the polyester structural unit may be a structural unit remaining after removing two or more hydroxyl groups from the polyol compound containing a polyester structure. The polyol compound containing a polyester structure may be a commercially available product, and examples of such commercial products include VYLON (registered trademark) manufactured by Toyobo Co., Ltd., POLYESTER (registered trademark) manufactured by Nippon Synthetic Chemical Industry Co., Ltd., and Silak (registered trademark) manufactured by Resonac Co., Ltd.
[0075] The poly(meth)acrylic acid structural unit refers to a structural unit containing a plurality of "at least one of an acrylic acid structure and a methacrylic acid structure". For example, when a polyol compound having a flexible skeleton (a polyol compound containing a poly(meth)acrylic acid structure in this embodiment) is used to manufacture resin X as described later, the poly(meth)acrylic acid structural unit may be a remaining structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing a poly(meth)acrylic acid structure. Commercially available products may be used as the polyol compound containing a poly(meth)acrylic acid structure. Examples of such commercially available products include TEISANRESIN "SG-600TEA" and "SG-790" (hydroxyl-containing acrylate copolymer resins) manufactured by Nagase ChemteX Co., Ltd. and "W-197C" (hydroxyl-containing acrylate copolymer resin) manufactured by Negami Industries Co., Ltd.
[0076] Examples of the polysiloxane structural unit include a dialkyl polysiloxane structural unit, a diaryl polysiloxane structural unit, a monoalkyl monoaryl polysiloxane structural unit, and a monoalkyl polysiloxane structural unit.
[0077] For example, when the resin X is produced using a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polysiloxane structure) as described later, the polysiloxane structural unit may be a structural unit remaining after two or more hydroxyl groups are removed from the polyol compound containing a polysiloxane structure. A commercially available product may be used as the polyol compound containing a polysiloxane structure, and examples of such commercial products include "X-21-5841" and "KF-9701" (hydroxyl-terminated polysiloxane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0078] As described above, resin X comprises an oligophenylene ether skeleton and a flexible skeleton. The mass ratio of the oligophenylene ether skeleton to the flexible skeleton in resin X (flexible skeleton / oligophenylene ether skeleton) is preferably 0.2 or more, more preferably 0.4 or more, and more preferably 0.5 or more, 0.6 or more, or 0.7 or more, in combination with a thermosetting resin and an inorganic filler, from the viewpoint of bringing a cured product that can further suppress warping, present better dielectric properties, and better maintain mechanical strength when exposed to a high temperature and high humidity environment. The conditions of the mass ratio may be, for example, 3 or less, 2.5 or less, 2 or less, etc.
[0079] The resin X has a glass transition temperature of 25°C or less. If the resin X has only one glass transition temperature, the glass transition temperature is 25°C or less. If the resin X has multiple glass transition temperatures, at least one glass transition temperature is 25°C or less. When the resin X has multiple glass transition temperatures, there is no particular limitation on the other glass transition temperatures as long as the resin X has a glass transition temperature of 25°C or less. In combination with a thermosetting resin and an inorganic filler, from the viewpoint of providing a cured product that can further suppress warping, exhibit better dielectric properties, and better maintain mechanical strength when exposed to a high temperature and high humidity environment, the glass transition temperature of the resin X below 25°C is preferably 10°C or less, more preferably 5°C or less, and even more preferably 0°C or less.
[0080] In the present invention, the glass transition temperature of the resin X is based on a value measured by DSC (differential scanning calorimetry) at a temperature increase rate of 5° C. / min.
[0081] From the viewpoint of being able to enjoy the effects of the present invention, the weight average molecular weight Mw of the resin X is preferably 5,000 or more, more preferably 10,000 or more, further preferably 20,000 or more, 40,000 or more, 60,000 or more, 80,000 or more, or 100,000 or more. The upper limit of the Mw is not particularly limited, but is usually less than 1,000,000, preferably less than 800,000, more preferably less than 600,000, and further preferably less than 500,000.
[0082] In the present invention, the weight average molecular weight Mw of the resin X is a value based on polystyrene conversion measured by gel permeation chromatography (GPC).
[0083] -Synthesis of Resin X- As long as the resin X can realize a structure including the above-mentioned oligophenylene ether skeleton and the flexible skeleton, the synthesis procedure thereof is not particularly limited.
[0084] An example of the synthesis procedure of the resin X is shown below.
[0085] In one embodiment, the resin X is obtained by making (x1) a polyol compound having a flexible skeleton, (x2) polyisocyanate compounds, (x3) a compound containing an acid anhydride group, and (x4) a polyol compound containing an oligophenylene ether skeleton Obtained by reaction.
[0086] In the reaction, the flexible skeleton of component (x1) is bonded to the oligophenylene ether skeleton of component (x4) via the imide structure (preferably a cyclic imide structure) generated by the reaction of component (x2) and component (x3). Therefore, in one embodiment, resin X contains an imide structure (preferably a cyclic imide structure).
[0087] Regarding the component (x1), preferred examples of the flexible skeleton are as described above. As the component (x1), any polyol compound containing a flexible skeleton can be used according to the structure of the target resin X (i.e., the flexible skeleton), and examples of commercial products thereof are as described above with respect to the flexible skeleton. The component (x1) can be used alone or in combination of two or more, depending on the type of the flexible skeleton contained in the resin X.
[0088] The polyisocyanate compound as component (x2) is not particularly limited in type as long as it can react with a hydroxyl group and react with component (x3) to form an imide structure. Examples of the polyisocyanate compound include aliphatic diisocyanate compounds such as butane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; alicyclic diisocyanate compounds such as norbornane diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate; phenylene diisocyanate (p-phenylene diisocyanate, m-phenylene diisocyanate), xylene diisocyanate (p-xylene diisocyanate, m-xylene diisocyanate), toluene diisocyanate (toluene-2 ,4-diisocyanate, toluene-2,6-diisocyanate), 4,4'-diphenylmethane diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, 3,3'-diethyldiphenyl-4,4'-diisocyanate, m-xylene diisocyanate, 1,3-bis(α,α-dimethylisocyanatomethyl)benzene, tetramethylxylene diisocyanate, diphenyl ether-4,4'-diisocyanate, naphthalene diisocyanate and other aromatic diisocyanate compounds, polymethylene polyphenyl polyisocyanate, their isocyanurate modified products, biuret modified products, allophanate modified products, etc. Component (x2) may be used alone or in combination of two or more.
[0089] As the compound containing anhydride groups as component (x3), as long as it can react with component (x2) to form an imide structure (preferably a cyclic imide structure), its type is not particularly limited. As the compound containing anhydride groups, tetracarboxylic dianhydride can be preferably used, and examples thereof include pyromellitic dianhydride, benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic anhydride, p-phenylene trimellitic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, cyclobutane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, 3,3'-4,4'-diphenyl sulfone tetracarboxylic dianhydride, and 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione. The component (x3) may be used alone or in combination of two or more.
[0090] Regarding the component (x4), preferred examples of oligophenylene ether skeletons are as described above. As the component (x4), any polyol compound containing an oligophenylene ether skeleton can be used according to the structure of the target resin X (i.e., the oligophenylene ether skeleton). For example, as a polyol compound containing an oligophenylene ether skeleton represented by the above formula (2-1), "NORYL SA90" manufactured by Sabic Innovative Plastics can be cited. The component (x4) can be used alone or in combination of two or more, depending on the type of oligophenylene ether skeleton contained in the resin X.
[0091] The synthesis reaction of the resin X using these (x1) to (x4) components can be carried out under the conditions generally used in the imidization reaction using a polyol compound, an isocyanate compound and an anhydride group-containing compound. The reaction raw materials containing the (x1) to (x4) components can be reacted together, or the (x1) to (x4) components can be reacted in sequence. When the reaction raw materials containing the (x1) to (x4) components are reacted together, the reaction temperature can be set to, for example, a range of 100 to 160° C., and the reaction time can be set to, for example, a range of 4 to 10 hours. In addition, when the (x1) to (x4) components are reacted in sequence, the (x1) component and the (x2) component can be reacted at, for example, a range of 50 to 100° C. for 0.5 to 4 hours, and then the (x3) component and the (x4) component can be added and reacted at, for example, a range of 120 to 160° C. for 3 to 6 hours.
[0092] A catalyst may be used in the reaction of components (x1) to (x4). Examples of the catalyst include tertiary amines such as tetramethylbutylene diamine, benzyl dimethylamine, triethanolamine, triethylamine, N,N'-dimethylpiperidine, α-methylbenzyl dimethylamine, N-methylmorpholine, and triethylenediamine, and organic metal catalysts such as dibutyltin laurate, dimethyltin dichloride, cobalt naphthenate, and zinc naphthenate.
[0093] In the above reaction, by changing the degree of reaction between component (x1) and component (x2) and the quantitative ratio of component (x1) to component (x4), the molecular weight of resin X and the proportion of the flexible skeleton in resin X, and thus the glass transition temperature of resin X, can be adjusted.
[0094] From the viewpoint of bringing a cured product that can further suppress warping, present better dielectric properties, and better maintain mechanical strength when exposed to a high temperature and high humidity environment, the mass ratio of resin X to inorganic filler (resin X / inorganic filler) is preferably 0.03 or more, more preferably 0.05 or more, more preferably 0.06 or more, 0.08 or more, 0.1 or more, 0.1 or more, 0.12 or more, 0.14 or more, or 0.15 or more. When the mass ratio of resin X / inorganic filler is more than 0.1, it is easy to obtain a cured product with excellent dielectric loss tangent, warping, and reliability, which is preferred. From the same viewpoint, the upper limit of the mass ratio is preferably less than 0.5, more preferably less than 0.4, and more preferably less than 0.3.
[0095] From the viewpoint of being able to enjoy the effect of the present invention more, the content of the resin X in the resin composition, when the resin component in the resin composition is set to 100% by mass, is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, further more preferably 20% by mass or more, 22% by mass or more, 24% by mass or more, or 25% by mass or more, and its upper limit is preferably 66% by mass or less, 64% by mass or less, or 62% by mass or less, more preferably 60% by mass or less, or less than 60% by mass, further preferably 55% by mass or less, 50% by mass or less, 48% by mass or less, 46% by mass or less, or 45% by mass or less. Therefore, in one embodiment, when the resin component in the resin composition is set to 100% by mass, the content of the resin X is 10% by mass or more and less than 60% by mass.
[0096] <Curing agent> The resin composition of the present invention may further contain a curing agent.
[0097] As a curing agent, there is no particular limitation, and examples thereof include active ester curing agents, phenol curing agents, naphthol curing agents, carbodiimide curing agents, anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate curing agents, and thiol curing agents. One type of curing agent can be used alone, or two or more types can be used in combination. From the viewpoint of being able to enjoy the effect of the present invention more, the curing agent is preferably selected from one or more of active ester curing agents, phenol curing agents, and carbodiimide curing agents.
[0098] As active ester curing agent, a compound having more than one active ester group in one molecule can be used. Among them, as active ester curing agent, preferably a compound having more than two highly reactive ester groups in one molecule such as esters of phenolic esters, thiophenolic esters, N-hydroxylamine esters, and heterocyclic hydroxy compounds. The active ester curing agent is preferably a curing agent obtained by the condensation reaction of a carboxylic acid compound and / or a thiocarboxylic acid compound with a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improved heat resistance, it is preferably an active ester curing agent derived from a carboxylic acid compound, more preferably an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound, and further more preferably an active ester curing agent obtained from a carboxylic acid compound and an aromatic hydroxy compound.
[0099] As the carboxylic acid compound, any of an aromatic carboxylic acid compound and an aliphatic carboxylic acid compound can be used, and examples thereof include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and halides thereof.
[0100] Examples of the aromatic hydroxy compound include (i) addition polymerization products of unsaturated aliphatic cyclic compounds having two double bonds in one molecule and phenols, (ii) various bisphenol compounds, (iii) aromatic polyols having two or more hydroxyl groups bonded to carbon atoms on the aromatic ring, and (iv) aromatic monohydric alcohols having one hydroxyl group bonded to carbon atoms on the aromatic ring. Examples of the addition polymerization products of unsaturated aliphatic cyclic compounds and phenols include addition polymerization products of unsaturated aliphatic cyclic compounds such as dicyclopentadiene, tetrahydroindene, norbornadiene, limonene, and vinylcyclohexene and phenols which may have a substituent (e.g., phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halogenated phenol, etc.), and specifically, examples include dicyclopentadiene-phenol addition polymerization products. Examples of the bisphenol compound include bisphenol A, bisphenol F, bisphenol AF, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, and bisphenol M. Examples of the aromatic polyol having two or more hydroxyl groups bonded to carbon atoms on an aromatic ring include hydroquinone, resorcinol, catechol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, and phenolic novolac resin. Examples of the aromatic monohydric alcohol having one hydroxyl group bonded to a carbon atom on the aromatic ring include phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halogenated phenols, naphthol, methylnaphthol, dimethylnaphthol, ethylnaphthol, propylnaphthol, vinylnaphthol, allylnaphthol, phenylnaphthol, benzylnaphthol, halogenated naphthols, and the like.
[0101] Preferred specific examples of active ester curing agents include active ester compounds containing dicyclopentadiene diphenol structures, active ester compounds containing naphthalene structures, active ester compounds containing acetylated products of linear phenolic resins, and active ester compounds containing benzoylated products of linear phenolic resins. Among them, active ester compounds containing naphthalene structures and active ester compounds containing dicyclopentadiene diphenol structures are more preferred. "Dicyclopentadiene diphenol structure" means a divalent structural unit formed by phenylene-dicyclopentylene-phenylene.
[0102] As commercially available products of active ester curing agents, there are "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", "HPC-8000H-65TM" (manufactured by DIC Corporation) as active ester compounds containing a dicyclopentadiene-type diphenol structure, "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", "HPC-8100H-65TM" (manufactured by DIC Corporation) as active ester compounds containing a naphthalene structure. "EXB-50-62T", "EXB-8" (manufactured by DIC Corporation), "EXB9401" (manufactured by DIC Corporation) as a phosphorus-containing active ester compound, "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound of an acetylated product of a linear phenolic resin, "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester compounds of a benzoylated product of a linear phenolic resin, and "PC1300-02-65MA" (manufactured by Airwater Corporation) as an active ester compound containing a styryl group and a naphthalene structure.
[0103] As phenolic curing agent and naphthol curing agent, from the viewpoint of heat resistance and water resistance, preferably, phenolic curing agent with phenolic structure or naphthol curing agent with phenolic structure. In addition, from the viewpoint of insulating layer having good adhesion strength (peel strength) with conductor layer, preferably, nitrogenous phenolic curing agent or nitrogenous naphthol curing agent, more preferably, phenolic curing agent containing triazine skeleton or naphthol curing agent containing triazine skeleton. Wherein, from the viewpoint of making heat resistance, water resistance and adhesion strength with conductor layer highly satisfied, preferably, phenolic novolac resin containing triazine skeleton or naphthol novolac resin containing triazine skeleton.
[0104] Specific examples of phenolic curing agents and naphthol curing agents include "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemicals; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", and "SN-375" manufactured by Nippon Steel Chemicals Co., Ltd. ", "SN-395"; "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", "KA-1165" manufactured by DIC Corporation; "GDP-6115L", "GDP-6115H", "ELPC 75" and other products manufactured by Qunrong Chemical Co., Ltd.
[0105] Examples of the carbodiimide curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides such as tetramethylene-bis(tert-butylcarbodiimide) and cyclohexanebis(methylene-tert-butylcarbodiimide); biscarbodiimides such as aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), poly(isophoronecarbodiimide); Polycarbodiimides; poly(phenylene carbodiimide), poly(naphthylene carbodiimide), poly(toluene carbodiimide), poly(methyl diisopropyl phenylene carbodiimide), poly(triethyl phenylene carbodiimide), poly(diethyl phenylene carbodiimide), poly(triisopropyl phenylene carbodiimide), poly(diisopropyl phenylene carbodiimide), poly(xylylene carbodiimide), poly(tetramethyl xylylene carbodiimide), poly(methylene diphenylene carbodiimide), poly[methylene bis(methyl phenylene) carbodiimide] and the like aromatic polycarbodiimides.
[0106] Examples of commercially available carbodiimide curing agents include "CARBODILITE V-02B", "CARBODILITE V-03", "CARBODILITE V-04K", "CARBODILITE V-07" and "CARBODILITE V-09" manufactured by Nisshinbo Chemical Co., Ltd. and "Stabaxol P", "Stabaxol P400" and "Hycasyl 510" manufactured by LANXESS.
[0107] As the acid anhydride curing agent, there can be mentioned a curing agent having one or more acid anhydride groups in one molecule, preferably a curing agent having two or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, dihydrophthalic anhydride, and the like. Polymer-type acid anhydrides such as benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride), styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, etc. Commercially available products of anhydride-based curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by Shin Nippon Rika Co., Ltd., "YH306" and "YH307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Risenoco Co., Ltd., and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Cray Valley Co., Ltd.
[0108] As the amine curing agent, there can be mentioned a curing agent having one or more, preferably two or more, amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., among which aromatic amines are preferred from the viewpoint of exerting the desired effect of the present invention. The amine curing agent is preferably a primary amine or a secondary amine, more preferably a primary amine. As specific examples of the amine curing agent, there can be mentioned 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, metaphenylenediamine, metaphenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxy phenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. As the amine curing agent, commercially available products can be used, for example, "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., "EPICURE W" manufactured by Mitsubishi Chemical Corporation, etc.
[0109] Specific examples of the benzoxazine curing agent include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Industry Co., Ltd., "HFB2006M" manufactured by Showa Highpolymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0110] Examples of cyanate curing agents include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by triazinizing a portion of these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Lonza Japan (both are linear phenolic resin-type multifunctional cyanate resins), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate is triazine-treated to form a trimer), etc.
[0111] Examples of the thiol-based curing agent include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0112] The reactive group equivalent of the curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the curing agent per 1 equivalent of reactive groups.
[0113] From the viewpoint of easily realizing the solidified material of low dielectric loss tangent, the curing agent preferably includes an active ester curing agent. When the curing agent includes an active ester curing agent, when the non-volatile component in the curing agent is set to 100% by mass, the content of the active ester curing agent is preferably 30% by mass or more, more preferably 40% by mass or more, further preferably 50% by mass or more or 60% by mass or more, and its upper limit can be 100% by mass, for example, it can also be 98% by mass or less, 95% by mass or less, or 90% by mass or less. According to the present invention using resin X, even in the case of not including the active ester curing agent or in the case of a small amount thereof, a solidified material of low dielectric loss tangent can be realized. For example, when the non-volatile component in the curing agent is set to 100% by mass, even in the case of less than 30% by mass, less than 25% by mass, less than 20% by mass, or in the case of 0% by mass (not containing), a solidified material of low dielectric loss tangent can also be brought.
[0114] When the resin composition of the present invention includes a curing agent, the content of the curing agent in the resin composition is not particularly limited, and when the resin component in the resin composition is set to 100% by mass, it is preferably 3% by mass or more, more preferably 5% by mass or more, and further preferably 10% by mass or more, 15% by mass or more, or 20% by mass or more. The upper limit of the content of the curing agent is preferably 60% by mass or less, more preferably 50% by mass or less, 45% by mass or less, 40% by mass or less, or 35% by mass or less.
[0115] <Curing accelerator> The resin composition of the present invention may further contain a curing accelerator. By containing a curing accelerator, the curing time and the curing temperature can be effectively adjusted.
[0116] Examples of the curing accelerator include phosphorus curing accelerators, urea curing accelerators, guanidine curing accelerators, imidazole curing accelerators, metal curing accelerators, and amine curing accelerators. From the perspective of being able to enjoy the effects of the present invention, the curing accelerator preferably includes an amine curing accelerator or an imidazole curing accelerator. The curing accelerator may be used alone or in combination of two or more.
[0117] Phosphorus curing accelerators include, for example, tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitic acid salt, tetrabutylphosphonium hydrogen hexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, di-tert-butylmethylphosphonium tetraphenylborate and other aliphatic phosphonium salts; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, para- Aromatic phosphonium salts such as tolyltriphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, etc.; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane, etc.; aromatic phosphine-quinone addition reactants such as triphenylphosphine-p-benzoquinone addition reactants, etc.; tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di- aliphatic phosphines such as tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine; dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tri(4-ethylphenyl)phosphine, tri(4-propylphenyl)phosphine, tri(4-isopropylphenyl)phosphine, tri(4-butylphenyl)phosphine, tri(4-tert-butylphenyl)phosphine, tri(2,4-dimethylphenyl)phosphine, tri(2,5-dimethylphenyl)phosphine, tri(2 ,6-dimethylphenyl)phosphine, tri(3,5-dimethylphenyl)phosphine, tri(2,4,6-trimethylphenyl)phosphine, tri(2,6-dimethyl-4-ethoxyphenyl)phosphine, tri(2-methoxyphenyl)phosphine, tri(4-methoxyphenyl)phosphine, tri(4-ethoxyphenyl)phosphine, tri(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, 2,2'-bis(diphenylphosphino)diphenyl ether and the like.
[0118] Examples of the urea curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, 3-(3,4-dimethylphenyl)-1, Aromatic dimethylureas such as 1-dimethylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluenebisdimethylurea], and the like.
[0119] Examples of the guanidine-based curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.
[0120] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1') imidazole compounds and adducts of imidazole compounds and epoxy resins such as 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline.
[0121] As the imidazole curing accelerator, commercially available products can be used, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2P4MZ", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; "P200-H50" manufactured by Mitsubishi Chemical Corporation, etc. These may be used alone or in combination of two or more.
[0122] As metal curing accelerators, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. Specific examples of organic metal complexes include organic cobalt complexes such as cobalt acetylacetonate (II), cobalt acetylacetonate (III), organic copper complexes such as copper acetylacetonate (II), organic zinc complexes such as zinc acetylacetonate (II), organic iron complexes such as iron acetylacetonate (III), organic nickel complexes such as nickel acetylacetonate (II), and organic manganese complexes such as manganese acetylacetonate (II). As organic metal salts, for example, zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.
[0123] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine (DMAP), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo[5.4.0]undecene. Amine-based curing accelerators may be commercially available products, such as "MY-25" manufactured by Ajinomoto Fine Chemicals Co., Ltd.
[0124] When the resin composition of the present invention contains a curing accelerator, the content of the curing accelerator in the resin composition is not particularly limited. When the resin component in the resin composition is set to 100% by mass, it is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and further preferably 0.05% by mass or more. The upper limit is preferably 3% by mass or less, more preferably 2% by mass or less, 1.5% by mass or less, or 1% by mass or less.
[0125] <Maleimide resin> The resin composition of the present invention may further contain a maleimide resin. The maleimide resin may be used alone or in combination of two or more.
[0126] The maleimide resin is preferably selected from (E1) maleimide resins containing an aliphatic group having 5 or more carbon atoms directly bonded to the nitrogen atom of the maleimide, (E2) one or more of a maleimide resin having a trimethylindane skeleton, and (E3) a maleimide resin having an aromatic ring directly bonded to a nitrogen atom of maleimide.
[0127] Here, the term "directly" means that no other group exists between the nitrogen atom of maleimide and the aliphatic group having 5 or more carbon atoms for the component (E1), and means that no other group exists between the nitrogen atom of maleimide and the aromatic ring for the component (E3).
[0128] Regardless of whether the maleimide resin is the component (E1), the component (E2) or the component (E3), it is preferred that the maleimide resin has two or more maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl) in one molecule.
[0129] Preferred embodiments of the maleimide resin are described below as the component (E1), the component (E2), and the component (E3). Hereinafter, the term "substituent" is as described in the above-mentioned <Explanation of Terms>.
[0130] <(E1)Component> The component (E1) is a maleimide resin containing an aliphatic group having 5 or more carbon atoms directly bonded to the nitrogen atom of maleimide. The maleimide resin can be obtained, for example, by subjecting a component containing an aliphatic amine compound (such as a dimer diamine compound), maleic anhydride, and, if necessary, tetracarboxylic dianhydride to an imidization reaction.
[0131] In one embodiment, the component (E1) contains a compound represented by the following formula (E1-1).
[0132] [Chemical formula 5]
[0133] In formula (E1-1), A 1 represents an aliphatic group having 5 or more carbon atoms which may have a substituent, L 1 represents a single bond or a divalent linking group, nB1 represents an integer from 0 to 20. 1 When there are multiple, they can be the same or different. 1 When there are multiple ones, they can be the same or different.
[0134] A 1 The carbon number of the aliphatic group represented by is 5 or more, preferably 10 or more, 15 or more, or 20 or more. The upper limit of the carbon number is not particularly limited, and may be, for example, 100 or less, 80 or less, 60 or less, or 50 or less. It should be noted that the carbon number does not include the carbon number of the substituent.
[0135] In one embodiment, A 1 It is a divalent group represented by the following formula (E1-2).
[0136] [Chemical formula 6]
[0137] In formula (E1-2), A 11 represents a single bond, an alkylene group or an alkenylene group (preferably an alkylene group or an alkenylene group), Ring Z 1 represents a non-aromatic ring optionally having a group selected from an alkyl group and an alkenyl group (preferably a cycloalkane ring or a cycloalkene ring optionally having a group selected from an alkyl group and an alkenyl group), nB11 represents an integer of 0 to 3 (preferably 0 or 1, more preferably 1) * indicates the binding site. 11 and Ring Z 1 Each independently optionally has a substituent.11 When there are multiple, they can be the same or different. 1 When there are multiple ones, they can be the same or different.
[0138] As L 1 The divalent connecting group represented by the invention may be a divalent organic group (preferably an organic group containing a divalent ring (e.g., an aromatic ring or a non-aromatic ring)) containing two or more (e.g., 2 to 3000, 2 to 1000, 2 to 100, 2 to 50) skeletal atoms selected from carbon atoms, oxygen atoms, nitrogen atoms and sulfur atoms, among which a divalent group represented by the following formula (E1-3) is preferred.
[0139] [Chemical formula 7]
[0140] In formula (E1-3), A 12 represents a single bond, or a divalent group containing one or more (e.g., 1 to 3000, 1 to 1000, 1 to 100, or 1 to 50) skeletal atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, and sulfur atoms, R B1 and R B2 Each independently represents a substituent, nB12 means 0 or 1, nB13 and nB14 each independently represent an integer of 0 to 3 (preferably 0 or 1), * indicates the binding site. B1 When there are multiple, they can be the same or different. B2 When there are multiple ones, they may be the same or different.
[0141] It should be noted that when nB12 is 0, the divalent group represented by formula (E1-3) represents a divalent group having a structure represented by the following formula (E1-4). B1 , nB13 and * are as described in formula (E1-3).
[0142] [Chemical formula 8]
[0143] In formula (E1-3), in the embodiment where nB12 is 1, 12 The divalent group represented is preferably a divalent group represented by the following formula (E1-5).
[0144] [Chemical formula 9]
[0145] In formula (E1-5), Y 1 represents a single bond, an alkylene group, an alkenylene group, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, -NHCO-, -COO- or -OCO-, Ring Z 2 represents a non-aromatic ring optionally having a substituent or an aromatic ring optionally having a substituent, nB15 represents an integer of 0 to 5 (preferably 0 to 3), * indicates the binding site. 1 and Ring Z 2 Each independently optionally has a substituent. 1 When there are multiple, they can be the same or different. 2 When there are multiple ones, they can be the same or different.
[0146] As A 12 Specific examples of the divalent group represented are not particularly limited, and include -CH2-, -CH(CH3)-, -CH(CH2CH3)-, -C(CH3)2-, -C(CH3)(CH2CH3)-, -C(CH2CH3)2-, -O-, -CO-, -S-, -SO- and -SO2-, and also include the divalent organic groups shown below. [Chemical formula 10]
[0147] The weight average molecular weight (Mw) of the component (E1) is not particularly limited, but is preferably 150 to 50,000, more preferably 300 to 20,000. More specifically, in the form where nB1 in the formula (E1-1) is an integer greater than 1, it is preferably 500 to 50,000, more preferably 1,000 to 20,000, and in the form where nB1 is 0, it is preferably 150 to 5,000, more preferably 300 to 1,000. The Mw of the component (E1) can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).
[0148] In addition, for the (E1) component, the functional group equivalent of the maleimide group is preferably 50 to 20,000 g / eq., and more preferably 100 to 20,000 g / eq. In more detail, in the form where nB1 in the formula (E1-1) is an integer greater than 1, it is preferably 300 g / eq. to 20,000 g / eq., and more preferably 500 g / eq. to 10,000 g / eq. In the form where nB1 is 0, it is preferably 50 g / eq. to 2,000 g / eq., and more preferably 100 g / eq. to 1,000 g / eq., further preferably 200 g / eq. to 600 g / eq., and particularly preferably 300 g / eq. to 400 g / eq.
[0149] In combination with resin X, from the viewpoint of producing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment, component (E1) preferably comprises a maleimide resin having any one of the structures represented by the following formula (E1-6), the structures represented by the following formula (E1-7), or the structures represented by the following formula (E1-8).
[0150] [Chemical formula 11]
[0151] In formula (E1-6), A 11 and Ring Z 1 As mentioned above, A 11 -Ring Z 1 -A 11 The number of carbon atoms per block is preferably 20 to 100 (more preferably 30 to 60 or 30 to 50), and a so-called dimer acid skeleton (C36 skeleton; C36 alkylene skeleton derived from dimer diamine) is particularly preferred. nB16 represents an integer of 1 to 10.
[0152] [Chemical formula 12] In formula (E1-7), A 11 , Y 1 、Ring Z 1 、Ring Z 2 As mentioned above, nB15 11 -Ring Z 1 -A 11 The number of carbon atoms per block is preferably 20 to 100 (more preferably 30 to 60 or 30 to 50), and the so-called dimer acid skeleton (C36 skeleton; C36 alkylene skeleton derived from dimer diamine) is particularly preferred. In addition, the block formed by nB15+1 Y1 and nB15 ring Z2 corresponds to the divalent group A described above. 12Among them, a divalent group containing an oxygen atom is preferred. nB17 represents an integer of 1-10.
[0153] [Chemical formula 13]
[0154] In formula (E1-8), A 11 and Ring Z 1 As mentioned above, A 11 -Ring Z 1 -A 11 The number of carbon atoms per block is preferably 20 to 100 (more preferably 30 to 60 or 30 to 50), and a so-called dimer acid skeleton (C36 skeleton; C36 alkylene skeleton derived from dimer diamine) is particularly preferred. nB11 represents an integer of 0-10.
[0155] Commercially available products of maleimide resins having a structure represented by formula (E1-6) include, for example, "BMI-3000J" and "BMI-5000" manufactured by Designer Molecules Inc. Commercially available products of maleimide resins having a structure represented by formula (E1-7) include, for example, "BMI-1400", "BMI-1500", and "BMI-1700" manufactured by Designer Molecules Inc. Commercially available products of maleimide resins having a structure represented by formula (E1-8) include, for example, "BMI-689" manufactured by Designer Molecules Inc.
[0156] <(E2) Ingredients> The component (E2) is a maleimide resin containing a trimethylindane skeleton. The trimethylindane skeleton is a skeleton represented by the following formula (E2-1).
[0157] [Chemical formula 14]
[0158] The benzene ring in the trimethylindane skeleton optionally has a substituent. When the benzene ring in the trimethylindane skeleton has a substituent, the number of the substituent may be 1 or more than 2. The upper limit of the number of substituents that the benzene ring in the trimethylindane skeleton has is usually less than 3. When the number of substituents is more than 2, they may be the same or different from each other. Among them, the benzene ring in the trimethylindane skeleton preferably has no substituent.
[0159] The number of trimethylindane skeletons contained in one molecule of the component (E2) may be 1 or 2 or more. The upper limit may be, for example, 10 or less, 8 or less, 7 or less, or 6 or less.
[0160] In addition to the above-mentioned trimethylindane skeleton, the component (E2) preferably further contains an aromatic ring skeleton. As the aromatic ring skeleton, it can be any of a carbocyclic skeleton and a heterocyclic skeleton, but a carbocyclic skeleton is more preferred. The number of ring carbons in the aromatic ring skeleton is preferably 3 to 20, more preferably 4 to 16, 5 to 14 or 6 to 10. As the aromatic ring skeleton, for example, a benzene ring skeleton, a naphthalene ring skeleton, an anthracene ring skeleton, etc. can be mentioned. The number of aromatic ring skeletons contained in one molecule of the component (E2) is preferably 1 or more, more preferably 2 or more, preferably 6 or less, more preferably 4 or less, and further preferably 3 or less. When the component (E2) contains two or more aromatic ring skeletons in addition to the trimethylindane skeleton, these aromatic ring skeletons may be the same as or different from each other.
[0161] The aromatic ring skeleton optionally has a substituent. When the aromatic ring skeleton has a substituent, the number of the substituent may be 1 or more than 2. The upper limit of the number of substituents possessed by the aromatic ring skeleton is usually less than 4. When the number of substituents is more than 2, they may be the same as or different from each other.
[0162] In addition to the trimethylindane skeleton, the component (E2) preferably further comprises a divalent aliphatic hydrocarbon group. In particular, when the component (E2) further comprises an aromatic ring skeleton in addition to the benzene ring in the trimethylindane skeleton, the component (E2) preferably comprises a divalent aliphatic hydrocarbon group. In this case, the divalent aliphatic hydrocarbon group preferably connects the benzene ring in the trimethylindane skeleton to the aromatic ring skeleton. In addition, the divalent aliphatic hydrocarbon group preferably connects the aromatic ring skeletons to each other.
[0163] The number of carbon atoms in the divalent aliphatic hydrocarbon group is preferably 1 or more, preferably 12 or less, more preferably 8 or less, and further preferably 5 or less. The divalent aliphatic hydrocarbon group may be any of a divalent saturated hydrocarbon group and a divalent unsaturated hydrocarbon group, preferably a divalent saturated hydrocarbon group, and more preferably an alkylene group. Examples of the divalent aliphatic hydrocarbon group include straight-chain alkylene groups such as methylene, ethylene, trimethylene, tetramethylene, pentamethylene, and hexamethylene; and branched alkylene groups such as ethylidene (-CH(CH3)-), propylidene (-CH(CH2CH3)-), isopropylidene (-C(CH3)2-), ethylmethylmethylene (-C(CH3)(CH2CH3)-), and diethylmethylene (-C(CH2CH3)2-). When the component (E2) contains two or more divalent aliphatic hydrocarbon groups in addition to the trimethylindane skeleton, these divalent aliphatic hydrocarbon groups may be the same as or different from each other.
[0164] In combination with resin X, from the viewpoint of providing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength when exposed to a high temperature and high humidity environment, component (E2) preferably includes a structure represented by the following formula (E2-2). Component (E2) may have the structure represented by formula (E2-2) as a whole, or may have a part of component (E2) have the structure represented by formula (E2-2).
[0165] [Chemical formula 15]
[0166] In formula (E2-2), Ar a1 represents a divalent aromatic ring group which may have a substituent, R a1 and R a2 Each independently represents a substituent, R a3 represents a divalent aliphatic hydrocarbon group, n a1 represents a positive integer, n a2 Each independently represents an integer from 0 to 4, n a3 Each independently represents an integer from 0 to 3. a1 When there are multiple, they can be the same or different. a2 When there are multiple R a3 They may be the same as or different from each other.
[0167] Ar a1 It represents a divalent aromatic ring group which may optionally have a substituent. The number of carbon atoms of the divalent aromatic ring group is preferably 6 or more, preferably 20 or less, more preferably 16 or less, 14 or less, or 10 or less. Examples of the divalent aromatic ring group include phenylene and naphthylene. Examples of the substituents which the divalent aromatic ring group may optionally have include the above-mentioned substituents, among which preferred are alkyl groups having 1 to 10 carbon atoms, alkoxy groups having 1 to 10 carbon atoms, alkylthio groups having 1 to 10 carbon atoms, aryl groups having 6 to 10 carbon atoms, aryloxy groups having 6 to 10 carbon atoms, arylthio groups having 6 to 10 carbon atoms, cycloalkyl groups having 3 to 10 carbon atoms, halogen atoms, hydroxyl groups, and mercapto groups. The hydrogen atoms of each substituent may be further substituted by halogen atoms. When the divalent aromatic ring group has a substituent, the number of the substituents is preferably 1 to 4. When the number of substituents the divalent aromatic ring group has is 2 or more, the two or more substituents may be the same as or different from each other. a1 It is preferably a divalent aromatic ring group having no substituent.
[0168] R a1 represents a substituent. a1 The substituent represented by , includes the above-mentioned substituents, among which preferred are alkyl groups having 1 to 10 carbon atoms, alkoxy groups having 1 to 10 carbon atoms, alkylthio groups having 1 to 10 carbon atoms, aryl groups having 6 to 10 carbon atoms, aryloxy groups having 6 to 10 carbon atoms, arylthio groups having 6 to 10 carbon atoms, cycloalkyl groups having 3 to 10 carbon atoms, halogen atoms, nitro groups, hydroxyl groups and mercapto groups. The hydrogen atoms of each substituent may be further substituted with halogen atoms.
[0169] Among them, R a1 More preferably, it is one or more groups selected from an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group having 6 to 10 carbon atoms, and still more preferably, it is an alkyl group having 1 to 4 carbon atoms.
[0170] R a2 represents a substituent. a2 The substituent represented by , includes the above-mentioned substituents, among which preferred are alkyl groups having 1 to 10 carbon atoms, alkoxy groups having 1 to 10 carbon atoms, alkylthio groups having 1 to 10 carbon atoms, aryl groups having 6 to 10 carbon atoms, aryloxy groups having 6 to 10 carbon atoms, arylthio groups having 6 to 10 carbon atoms, cycloalkyl groups having 3 to 10 carbon atoms, halogen atoms, hydroxyl groups and mercapto groups. The hydrogen atoms of each substituent may be further substituted with halogen atoms.
[0171] Among them, R a2 More preferably, it is one or more groups selected from an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group having 6 to 10 carbon atoms.
[0172] R a3 represents a divalent aliphatic hydrocarbon group. The preferred range of the divalent aliphatic hydrocarbon group is as described above.
[0173] n a1 Represents a positive integer. n a1 It is preferably 1 or more, preferably 10 or less, and more preferably 8 or less.
[0174] n a2 Each independently represents an integer from 0 to 4. a2 Preferably it is 2 or 3, more preferably 2. Multiple n a2 can be different, but are preferably the same as each other. a2 When it is 2 or more, multiple R a1 They may be the same as or different from each other.
[0175] n a3 represents an integer from 0 to 3. a3When there are plural, they may be different, but are preferably the same as each other. a3 Preferably 0.
[0176] In combination with resin X, from the viewpoint of providing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength when exposed to a high temperature and high humidity environment, component (E2) further preferably includes a structure represented by the following formula (E2-3). Component (E2) may have the structure represented by formula (E2-3) in its entirety, or may have a structure represented by formula (E2-3) in part.
[0177] [Chemical formula 16]
[0178] In formula (E2-3), R a1 , R a2 、n a1 、n a2 and n a3 As described in formula (E2-2).
[0179] The component (E2) may further include a structure represented by the following formula (E2-4).
[0180] [Chemical formula 17]
[0181] In formula (E2-4), R a1 , R a2 、n a2 and n a3 As described in formula (E2-2). In addition, n c1 is the number of repeating units, and represents an integer from 1 to 20. * represents a chemical bond.
[0182] For example, in the formula (E2-2), n a2 The number of R is 3 or less, and at least two of the ortho and para positions of the maleimide group-bonding positions of the benzene ring to which the maleimide group is bonded are not bonded. a1 In the case of, it can be combined with the structure represented by formula (E2-2) to contain the structure represented by the above formula (E2-4).
[0183] For example, in the component (E2), in the formula (E2-3), n a2 The number of R is 3 or less, and at least two of the ortho and para positions of the maleimide group-bonding positions of the benzene ring to which the maleimide group is bonded are not bonded. a1 In the case of, it can be combined with the structure represented by formula (E2-3) to contain the structure represented by the above formula (E2-4).
[0184] The manufacturing method of component (E2) is not particularly limited, for example, it can be manufactured by the method described in the public technical report No. 2020-500211 of the Japanese Invention Association. According to the manufacturing method described in the public technical report No. 2020-500211 of the Japanese Invention Association, a maleimide resin having a distribution of the number of repeating units of the trimethylindane skeleton can be obtained. The maleimide resin obtained by the method contains the structure shown in the following formula (E2-5). Therefore, the maleimide resin may include a maleimide resin containing the structure shown in formula (E2-5).
[0185] [Chemical formula 18]
[0186] In formula (E2-5), R 1 , R 2 , n2 and n3 are respectively the same as R in formula (E2-2) a1 , R a2 、n a2 and n a3 The meanings are the same, and the preferred types and ranges are also the same. n1 represents the average number of repeating units of 0.95 to 10.0.
[0187] In formula (E2-5), n1 represents the average number of repeating units, which ranges from 0.95 to 10.0. According to the manufacturing method described in the Japanese Invention Association Public Technical Bulletin No. 2020-500211, a group of maleimide resins containing the structure shown in formula (E2-5) can be obtained. It can be seen from the fact that the average number of repeating units n1 in formula (E2-5) can be less than 1.00 that the maleimide resin containing the structure shown in formula (E2-5) obtained in this way may include a maleimide resin having a repeating unit number of 0 in the trimethylindane skeleton. To this end, the (E2) component can be obtained from the maleimide resin containing the structure shown in formula (E2-5) by purifying and removing the maleimide resin with 0 repeating units of the trimethylindane skeleton. The resin composition may only contain the obtained (E2) component, preferably without removing the maleimide resin with 0 repeating units of the trimethylindane skeleton. The resin composition contains the maleimide resin containing the structure shown in formula (E2-5).
[0188] In formula (E2-5), the average number of repeating units n1 is preferably 0.95 or more, more preferably 0.98 or more, further preferably 1.0 or more, particularly preferably 1.1 or more, preferably 10.0 or less, more preferably 8.0 or less, further preferably 7.0 or less, particularly preferably 6.0 or less. When the average number of repeating units n1 is within this range, the effect of the present invention can be significantly obtained.
[0189] Among them, the following examples can be given as specific structural examples of the component (E2).
[0190] [Chemical formula 19]
[0191] The maleimide resin containing the structure represented by formula (E2-5) may further contain the structure represented by formula (E2-4). For example, in the maleimide resin containing the structure represented by formula (E2-5), n2 is 3 or less, and R is not bonded to two or more of the ortho and para positions of the maleimide group bonding position of the benzene ring to which the maleimide group is bonded. 1 In the case of, it can be combined with the structure represented by formula (E2-5) to contain the structure represented by formula (E2-4).
[0192] For the maleimide resin containing the structure represented by formula (E2-5), the molecular weight distribution Mw / Mn calculated by gel permeation chromatography (GPC) is preferably within a specific range. Specifically, the molecular weight distribution Mw / Mn of the maleimide resin containing the structure represented by formula (E2-5) is preferably 1.0 to 4.0, more preferably 1.1 to 3.8, further preferably 1.2 to 3.6, and particularly preferably 1.3 to 3.4.
[0193] For the component (E2), the functional group equivalent of the maleimide group is preferably 50 g / eq. or more, more preferably 100 g / eq. or more, and further preferably 200 g / eq. or more, and is preferably 2000 g / eq. or less, more preferably 1000 g / eq. or less, and further preferably 800 g / eq. or less.
[0194] <(E3) Ingredients> The component (E3) is a maleimide resin having an aromatic ring directly bonded (bonded) to the nitrogen atom of maleimide. The maleimide resin can be obtained, for example, by subjecting a component containing an aromatic amine compound (aromatic diamine compound, etc.) and maleic anhydride to an imidization reaction.
[0195] In one embodiment, the component (E3) includes a compound represented by the following formula (E3-1).
[0196] [Chemical formula 20]
[0197] In formula (E3-1), Cyclic Ar 1 represents an aromatic ring which may have a substituent, L 2 represents a single bond or a divalent linking group, nB2 represents an integer of 1 to 100. 1 can be the same or different from each other, L 2 When there are multiple ones, they may be the same or different from each other.
[0198] As cyclic Ar 1 The aromatic ring represented by may be either a carbocyclic ring or a heterocyclic ring, and is more preferably a carbocyclic ring. 1 The number of carbon atoms in the aromatic ring represented by is preferably 3 to 20, more preferably 5 to 14 or 6 to 10. The number of carbon atoms does not include the number of carbon atoms in the substituent.
[0199] As L 2 The divalent linking group represented by is not particularly limited as long as it is a divalent group containing one or more (e.g., 1 to 3000, 1 to 1000, 1 to 100, 1 to 50) backbone atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, and sulfur atoms. For example, A in the aforementioned formula (E1-3) can be cited. 12 The divalent group described.
[0200] Among them, cyclic Ar 1 It is preferably an aromatic carbon ring having 6 to 10 carbon atoms which may have a substituent (more preferably a benzene ring which may have a substituent). 2 (L 2 If there are multiple, at least 1 L 2 ) is a divalent group having a biphenyl skeleton. Therefore, in one embodiment, the component (E3) has a biphenyl skeleton.
[0201] It should be noted that in the component (E3), the nitrogen atom of the maleimide is directly bonded to the aromatic ring. The bonding position of the maleimide to the aromatic ring is determined by the L bonded to the aromatic ring. 2 For example, when the aromatic ring is a benzene ring, the bonding position of maleimide to the benzene ring is based on the L bonded to the benzene ring. 2 As a basis, it may be any of the ortho-position, meta-position and para-position, and bonding to the para-position is preferred from the viewpoint of enjoying the effects of the present invention more.
[0202] In a preferred embodiment, the component (E3) includes a compound represented by the following formula (E3-2).
[0203] [Chemical formula 21]
[0204] In formula (E3-2), R B3 , R B4 , R B5 and RB6 Each independently represents a substituent, nB21 represents an integer from 1 to 100, nB22 and nB23 each independently represent an integer of 1 to 10, nB24 and nB25 each independently represent an integer of 0 to 3, nB26 and nB27 each independently represent an integer of 0 to 4. B3 When there are multiple, they can be the same or different from each other, which is important for R B4 , R B5 and R B6 Same here.
[0205] nB21 is preferably 1-50, more preferably 1-20, further preferably 1-5.
[0206] nB22 and nB23 are each independently preferably 1 to 6, more preferably 1 to 3, and even more preferably 1 or 2.
[0207] nB24 and nB25 are each independently preferably an integer of 0 to 2, and more preferably 0 or 1. When nB24 and nB25 are 1 or more, R B3 and R B4 The substituents represented are each independently preferably an alkyl group or an aryl group.
[0208] nB26 and nB27 are each independently preferably an integer of 0 to 2, and more preferably 0 or 1. When nB26 and nB27 are 1 or more, R B5 and R B6 The substituents represented are each independently preferably an alkyl group or an aryl group.
[0209] Among them, nB26 and nB27 are preferably 0. Therefore, in a preferred embodiment, the component (E3) includes a compound represented by the following formula (E3-3).
[0210] [Chemical formula 22]
[0211] In formula (E3-3), R B3 , R B4 , nB21, nB22, nB23, nB24 and nB25 are as described in formula (E3-2).
[0212] When the molecular weight of the component (E3) has a molecular weight distribution, the weight average molecular weight (Mw) is 500 or more, preferably 550 or more. The upper limit of the Mw is not particularly limited, but is preferably 5000 or less, more preferably 2500 or less. The Mw of the component (E3) can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).
[0213] In addition, the functional group equivalent of the maleimide group of the component (E3) is preferably 50 g / eq. to 2000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 150 g / eq. to 500 g / eq., particularly preferably 200 g / eq. to 300 g / eq.
[0214] In combination with resin X, component (E3) preferably contains a maleimide resin having a structure represented by the following formula (E3-4), from the viewpoint of producing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment.
[0215] [Chemical formula 23]
[0216] In formula (E3-4), nB21 is as described above.
[0217] Commercially available products of maleimide resins having a structure represented by formula (E3-4) include, for example, "MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd. Regarding component (E3), as a compound represented by formula (E3-1), "BMI-4000" manufactured by Yamato Chemicals Co., Ltd., "BMI-80" manufactured by KI Chemicals Co., Ltd., etc. may also be used.
[0218] When the resin combination of the present invention includes maleimide resin, the content of the maleimide resin in the resin combination, when the resin component in the resin combination is set to 100% by mass, is preferably more than 0.5% by mass, more preferably more than 1% by mass, further preferably more than 2% by mass, more than 4% by mass or more than 5% by mass. The upper limit of this content is not particularly limited, and can be determined according to the desired characteristics of the resin combination, for example, can be less than 30% by mass, less than 25% by mass or less than 20% by mass, etc.
[0219] <Optional Additives> The resin composition of the present invention may further contain any additives. Examples of such additives include thermoplastic resins such as phenoxy resins, polyvinyl acetal resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, and polyester resins; organic fillers such as rubber particles; free radical polymerization initiators such as peroxide-based free radical polymerization initiators and azo-based free radical polymerization initiators; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as Benton (bentonite) and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion enhancers such as urea silane; triazole-based Adhesion imparting agents such as adhesion imparting agents, tetrazole-based adhesion imparting agents, and triazine-based adhesion imparting agents; antioxidants such as hindered phenol-based antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (such as phosphate compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (such as melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (such as antimony trioxide); dispersants such as phosphate-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers; the content of such additives can be determined according to the characteristics required of the resin composition.
[0220] <Organic Solvents> The resin composition of the present invention may further contain an organic solvent as a volatile component. Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol ethyl ether acetate. Ether ester solvents such as acetate, γ-butyrolactone, and methyl methoxypropionate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The organic solvent may be used alone or in combination of two or more.
[0221] Resin combination of the present invention can be manufactured as follows: in any preparation container, add resin X, thermosetting resin, inorganic filler containing oligophenylene ether skeleton in any order and / or partly or entirely at the same time, add curing agent, curing accelerator, maleimide resin, other additives or organic solvent and mix as required in addition. In addition, in the process of adding each component and mixing, the temperature can be appropriately set, and heating and / or cooling can be carried out part of the time or all the time. In addition, in the process of adding and mixing or thereafter, the thermosetting resin composition can be stirred or vibrated with stirring devices or oscillating devices such as mixers and uniformly dispersed. In addition, while stirring or vibrating, deaeration can be carried out under low pressure conditions such as under vacuum.
[0222] The resin composition of the present invention comprises a thermosetting resin, an inorganic filler and a resin X having an oligophenylene ether skeleton and a glass transition temperature of 25°C or less, and the bolt pulling tightness of the cured product thereof is 600 kgf / cm 2 According to such a resin composition, a cured product can be obtained which can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment.
[0223] From the viewpoint of providing a cured product that can suppress warping, exhibit good dielectric properties, and maintain good mechanical strength even when exposed to a high temperature and high humidity environment, the cured product of the resin composition of the present invention has a bolt pull adhesion strength of 600 kgf / cm 2 The above is important. For example, according to the method described in the test conditions (1) of "2. Bolt pull test" described later, a bolt pin is bonded to the cured product layer of the resin composition of the evaluation substrate made using the resin composition of the present invention, and the bolt pin is pulled in a direction perpendicular to the main surface of the cured product layer at a speed of 2 kgf / sec using a bolt pull tester ("ROMULUS" manufactured by Quad Group Inc.) The load value (kgf / cm2) at the moment when the cured product layer is peeled off 2 ) (this value is evaluated as the close contact strength (bolt pull close contact strength)) is 600kgf / cm 2 Above, preferably 700kgf / cm 2 More preferably, 750 kgf / cm 2 Above, or 800kgf / cm 2 The upper limit of the bolt pull-on strength is not particularly limited, and may be, for example, 1200 kgf / cm 2 Below, 1150kgf / cm 2 Below, 1100kgf / cm 2 The following etc.
[0224] For the resin composition of the present invention, when a cured layer (insulating layer) of the resin composition is formed on a substrate such as a silicon wafer, warping can be suppressed. For example, when the warping amount of a laminate is measured by manufacturing the laminate as described in the <Warping Evaluation> column described later, the warping amount is preferably less than 2500 μm, more preferably less than 2000 μm, and further preferably less than 1800 μm, less than 1600 μm, or less than 1500 μm.
[0225] The cured product of the resin composition of the present invention can exhibit a low dielectric loss tangent. For example, as described in the <Determination of dielectric loss tangent> column described later, the dielectric loss tangent (Df) of the cured product of the resin composition when measured at 5.8 GHz and 23° C. can be preferably less than 0.004, more preferably 0.0038 or less, or 0.0036 or less, and further preferably 0.0035 or less.
[0226] For the resin composition of the present invention, even if its cured product can maintain good fracture strength after reliability test (HAST). For example, as described in the column of <Evaluation of fracture strength> described later, prepare the cured product of the resin composition of the present invention exposed to the HAST environment of high temperature and high humidity (130°C, 85%RH) for 100 hours and the cured product that is not exposed, according to Japanese Industrial Standard (JIS K7127), use Tensilon universal testing machine (Orientec company "RTC-1250A") to perform tensile test, and when the fracture strength (%) at 23°C is measured, the reduction rate of the fracture strength before and after HAST can be preferably less than 10%, more preferably less than 7%, and further preferably less than 5% or less than 4%.
[0227] The resin composition of the present invention can bring a cured product that can suppress warping, show good dielectric properties, and maintain good mechanical strength when exposed to a high temperature and high humidity environment. Therefore, the resin composition of the present invention is suitable for use as a resin composition for forming a sealing layer on a semiconductor chip in a semiconductor chip package (resin composition for semiconductor sealing). The resin composition of the present invention is also suitable for use as a resin composition for forming an insulating layer of a printed wiring board (resin composition for insulating layer of a printed wiring board), and is more suitable for use as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for interlayer insulating layer of a printed wiring board). The resin composition of the present invention can also be suitable for use in the case where the printed wiring board is a component built-in circuit board. The resin composition of the present invention can also be suitable for use as a resin composition for forming an insulating layer of a rewiring substrate in a semiconductor chip package (resin composition for insulating layer of a rewiring substrate). It should be noted that in the present invention, a printed wiring board or a rewiring substrate is collectively referred to as a "circuit substrate", and therefore, the resin composition of the present invention can be suitable for use as an insulating layer of a circuit substrate.
[0228] The resin composition of the present invention can also be widely used in applications requiring a resin composition, such as resin sheets, sheet-like laminated materials such as prepregs, solder resists, underfill materials, die bonding materials, hole filling resins, sealing resins, and component embedding resins.
[0229] [Sheet-like laminated materials (resin sheets, prepregs)] The resin composition of the present invention may be used as it is, or may be used in the form of a sheet-like laminated material containing the resin composition.
[0230] As the sheet-like laminated material, the following resin sheets and prepregs are preferred.
[0231] In one embodiment, the resin sheet includes a support and a layer of a resin composition provided on the support (hereinafter simply referred to as a "resin composition layer"), wherein the resin composition layer is formed of the resin composition of the present invention.
[0232] The thickness of the resin composition layer is different from the preferred value according to the purpose, and can be appropriately determined according to the purpose. For example, from the viewpoint of the thinning of a printed wiring board or a semiconductor chip package, the thickness of the resin composition layer is preferably less than 400 μm, less than 300 μm, less than 200 μm, less than 100 μm, less than 80 μm, less than 60 μm, less than 50 μm, less than 40 μm or less than 30 μm. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be more than 1 μm, more than 5 μm, etc.
[0233] Examples of the support include thermoplastic resin films, metal foils, and release papers, and thermoplastic resin films and metal foils are preferred. Therefore, in a preferred embodiment, the support is a thermoplastic resin film or a metal foil.
[0234] When a thermoplastic resin film is used as a support, examples of the thermoplastic resin include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylic polymers such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0235] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. The copper foil may be a foil made of a single metal such as copper or an alloy of copper and other metals (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0236] For the support, the surface bonded to the resin composition layer may also be subjected to matte treatment, corona treatment, and antistatic treatment. In addition, as the support, a support with a release layer having a release layer on the surface bonded to the resin composition layer may also be used. As a release agent used in the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins may be cited. The support with a release layer may also use commercial products, for example, "SK-1", "AL-5", "AL-7" made by Lindec Corporation of a PET film having a release layer with an alkyd resin-based release agent as the main component, "Lumirror T60" made by Toray Industries, "Purex" made by Teijin, "Unipeel" made by Unitika, etc.
[0237] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.
[0238] When a metal foil is used as a support, a metal foil with a supporting substrate in which a peelable supporting substrate is bonded to a thin metal foil can be used. In one embodiment, the metal foil with a supporting substrate includes a supporting substrate, a peeling layer provided on the supporting substrate, and a metal foil provided on the peeling layer. When a metal foil with a supporting substrate is used as a support, the resin composition layer is provided on the metal foil.
[0239] In the metal foil with a supporting substrate, the material of the supporting substrate is not particularly limited, and examples thereof include copper foil, aluminum foil, stainless steel foil, titanium foil, copper alloy foil, etc. When copper foil is used as the supporting substrate, it may be electrolytic copper foil or rolled copper foil. In addition, the peeling layer is not particularly limited as long as the metal foil can be peeled off from the supporting substrate, and examples thereof include alloy layers of elements selected from Cr, Ni, Co, Fe, Mo, Ti, W, and P; organic films, etc.
[0240] In the metal foil with a supporting substrate, the material of the metal foil is preferably, for example, copper foil or copper alloy foil.
[0241] In the metal foil with a supporting substrate, the thickness of the supporting substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, more preferably in the range of 10 μm to 100 μm. The thickness of the metal foil may be, for example, in the range of 0.1 μm to 10 μm.
[0242] In one embodiment, the resin sheet may further include an arbitrary layer as required. As the arbitrary layer, for example, a protective film disposed on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support) may be cited. The thickness of the protective film is not particularly limited, for example, it may be 1 μm to 40 μm. By laminating the protective film, it is possible to suppress the attachment of garbage or the like on the surface of the resin composition layer or the generation of damage.
[0243] The resin sheet can be produced, for example, by directly coating a liquid resin composition on a support using a die coater or the like, or by preparing a resin varnish prepared by dissolving the resin composition in an organic solvent and coating the varnish on a support, followed by drying to form a resin composition layer.
[0244] Examples of the organic solvent include the same organic solvents as those described as components of the resin composition. The organic solvent may be used alone or in combination of two or more.
[0245] Drying can be carried out by known methods such as heating and hot air blowing. The drying conditions are not particularly limited, and the drying is carried out in a manner such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying conditions also vary depending on the boiling point of the organic solvent in the resin composition or resin varnish. For example, when using a resin composition or resin varnish containing 30% to 60% by mass of an organic solvent, the resin composition layer can be formed by drying at 50° C. to 150° C. for 3 minutes to 10 minutes.
[0246] The resin sheet can be stored by being rolled up into a roll. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0247] In one embodiment, the prepreg is formed by impregnating the resin composition of the present invention into a sheet-like fiber base material.
[0248] The sheet-like fiber substrate used for the prepreg is not particularly limited, and materials commonly used as prepreg substrates such as glass cloth, aramid nonwoven fabric, and liquid crystal polymer nonwoven fabric can be used. From the perspective of thinning of printed wiring boards or semiconductor chip packages, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.
[0249] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0250] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.
[0251] The sheet-like laminated material of the present invention can be suitable for forming a sealing layer on a semiconductor chip in a semiconductor chip package (for semiconductor sealing). The sheet-like laminated material of the present invention can also be suitable for forming an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more suitable for forming an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board). The sheet-like laminated material of the present invention can also be suitable for forming an insulating layer of a rewiring substrate in a semiconductor chip package (for an insulating layer of a rewiring substrate). That is, the sheet-like laminated material of the present invention can also be suitable for use as an insulating layer of a circuit substrate.
[0252] [Semiconductor chip packaging] The semiconductor chip package of the present invention comprises a cured product of the resin composition of the present invention.
[0253] In one embodiment, the semiconductor chip package of the present invention comprises a package substrate, a semiconductor chip mounted on the substrate, and a cured product of the resin composition of the present invention that seals at least a portion of the semiconductor chip. Hereinafter, this embodiment is also referred to as "embodiment A".
[0254] In Embodiment A, a conventionally known substrate for forming a semiconductor chip package can be used as the package substrate, and it may be manufactured in the same manner as a printed wiring board described later, for example.
[0255] The bonding conditions between the package substrate and the semiconductor chip may be any conditions that can connect the terminal electrodes of the semiconductor chip to the circuit wiring of the substrate by conductor connection. For example, the conditions used in flip-chip mounting of the semiconductor chip may be used.
[0256] As a bonding method, for example, a method of crimping a semiconductor chip to a substrate can be cited. As a crimping condition, the crimping temperature is usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and the crimping time is usually in the range of 1 second to 60 seconds (preferably 5 seconds to 30 seconds). In addition, as a bonding method, for example, a method of carrying a semiconductor chip on a substrate and performing reflow soldering for bonding can also be cited. The reflow soldering conditions can be set to a range of 120°C to 300°C.
[0257] After the semiconductor chip is bonded to the substrate, the gap between the semiconductor chip and the substrate can be filled with an underfill. The resin composition of the present invention can also be used as the underfill. In the case, the semiconductor chip package of the present invention includes an underfill formed by a cured product of the resin composition of the present invention.
[0258] The sealing of the semiconductor chip can be performed by the same method as step (3) in the embodiment B described later. As mentioned above, the resin composition of the present invention is useful as a sealing material for the semiconductor chip. In the above case, the semiconductor chip package of the present invention includes a sealing layer formed of a cured product of the resin composition of the present invention.
[0259] The resin composition of the present invention can be used as a molding underfill to fill a gap between a semiconductor chip and a substrate and seal the semiconductor chip at the same time.
[0260] When a semiconductor chip package is produced using the resin composition of the present invention, the resin composition of the present invention may be used as a liquid resin composition or in the form of a sheet-like laminate material as described above.
[0261] In another embodiment (hereinafter also referred to as "embodiment B"), the semiconductor chip package of the present invention can be manufactured, for example, using the resin composition of the present invention by a method including the following steps (1) to (6). In order to form the sealing layer of step (3) or the rewiring forming layer of step (5), the resin composition of the present invention can be used. Below, an example of using a resin composition to form a sealing layer and a rewiring forming layer is shown, but the technology for forming the sealing layer and the rewiring forming layer of a semiconductor chip package is well known, and anyone skilled in the art can use the resin composition of the present invention to manufacture a semiconductor chip package according to known techniques. (1) A step of laminating a temporary fixing film on a substrate; (2) A step of temporarily fixing the semiconductor chip on a temporary fixing film; (3) a step of forming a sealing layer on a semiconductor chip; (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring forming layer as an insulating layer on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off; and (6) A step of forming a rewiring layer as a conductor layer on the rewiring formation layer.
[0262] -Process (1)- The material used for the substrate is not particularly limited. Examples of the substrate include silicon wafers, glass wafers, glass substrates, metal substrates such as copper, titanium, stainless steel, and cold-rolled steel sheets (SPCC), substrates obtained by infiltrating epoxy resins or the like into glass fibers and heat-curing them (e.g., FR-4 substrates), and substrates formed from bismaleimide triazine resins (BT resins).
[0263] The temporary fixing film is not particularly limited as long as it is a material that can be peeled from the semiconductor chip in step (4) and can temporarily fix the semiconductor chip. Commercially available products can be used as the temporary fixing film. Examples of commercially available products include REVALPHA manufactured by Nitto Denko Corporation.
[0264] -Process (2)- The semiconductor chip is temporarily fixed on the temporary fixing film by bonding its electrode pad surface to the temporary fixing film. The temporary fixing of the semiconductor chip can be performed using a known device such as a flip chip welder and a mounter. The layout and number of semiconductor chips can be appropriately set according to the shape and size of the temporary fixing film, the production quantity of the target semiconductor package, etc. For example, they can be arranged in a matrix of multiple rows and columns for temporary fixing.
[0265] -Process (3)- The resin composition of the present invention is applied as a liquid composition on a semiconductor chip, and is cured (e.g., thermally cured) to form a sealing layer. Alternatively, the resin composition of the present invention can also be stacked on a semiconductor chip in the form of the above-mentioned resin sheet, and is cured (e.g., thermally cured) to form a sealing layer.
[0266] It should be noted that when used in the form of a resin sheet, the semiconductor chip and the resin sheet can be laminated by removing the protective film of the resin sheet and then heating and pressing the resin sheet to the semiconductor chip from the support body side. The semiconductor chip and the resin sheet can be laminated by a vacuum lamination method, and the lamination conditions are the same as those described later in the method for manufacturing a printed wiring board, and the preferred range is also the same.
[0267] After lamination, the resin composition is thermally cured to form a sealing layer. The thermal curing conditions are the same as those described later in the method for producing a printed wiring board.
[0268] The support of the resin sheet may be peeled off after laminating the resin sheet on the semiconductor chip and thermally curing it, or the support may be peeled off before laminating the resin sheet on the semiconductor chip.
[0269] When the resin composition of the present invention is applied as a liquid composition to form a sealing layer, the coating conditions may be the same as the coating conditions for forming a resin composition layer described for the resin sheet of the present invention. By using the resin composition of the present invention, good fluidity can be achieved at the coating / molding temperature.
[0270] -Process (4)- The method of peeling off the substrate and the temporary fixing film can be appropriately changed according to the material of the temporary fixing film, and examples thereof include a method of peeling off by heating and foaming (or expanding) the temporary fixing film, and a method of peeling off by irradiating ultraviolet rays from the substrate side to reduce the adhesion of the temporary fixing film.
[0271] In the method of peeling by heating and foaming (or expanding) the temporary fixing film, the heating conditions are usually 100 to 250°C for 1 to 90 seconds or 5 to 15 minutes. In the method of peeling by irradiating ultraviolet rays from the substrate side to reduce the adhesion of the temporary fixing film, the irradiation amount of ultraviolet rays is usually 10 mJ / cm 2 ~1000mJ / cm 2 .
[0272] -Process (5)- The material forming the rewiring forming layer (insulating layer) is not particularly limited as long as it has insulating properties when the rewiring forming layer (insulating layer) is formed, and is preferably a photosensitive resin or a thermosetting resin from the viewpoint of ease of manufacturing the semiconductor chip package. The resin composition of the present invention can also be well used for the formation of the rewiring forming layer.
[0273] After forming the rewiring formation layer, a through hole may be formed in the rewiring formation layer in order to provide interlayer connection between the semiconductor chip and the conductor layer described later. The through hole may be formed by a known method depending on the material of the rewiring formation layer.
[0274] -Process (6)- The material of the conductor layer formed on the rewiring formation layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above metals (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy) may be cited. Among them, from the viewpoints of versatility, cost, ease of pattern formation, etc., of the conductor layer formation, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper or an alloy layer of nickel-chromium alloy, copper-nickel alloy or copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is more preferred.
[0275] The conductor layer may be a single layer structure or a multilayer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. When the conductor layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium or an alloy layer of a nickel-chromium alloy.
[0276] The thickness of the conductor layer varies depending on the desired design of the semiconductor chip package, but is generally 1 μm to 35 μm, preferably 1 μm to 20 μm.
[0277] In one embodiment, the conductor layer can be formed by plating. For example, the surface of the rewiring forming layer can be plated by a conventionally known technique such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. From the perspective of manufacturing simplicity, it is preferably formed by a semi-additive method. An example of forming a conductor layer by a semi-additive method is shown below.
[0278] First, a plating seed layer is formed on the surface of the rewiring forming layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching, etc., so that a conductor layer (rewiring layer) having a desired wiring pattern can be formed.
[0279] It should be noted that the step (5) and the step (6) may be repeatedly performed to alternately stack (stack) the conductor layer (rewiring layer) and the rewiring forming layer (insulating layer).
[0280] When manufacturing a semiconductor chip package, (7) a step of forming a solder resist layer on a conductor layer (rewiring layer), (8) a step of forming bumps, and (9) a step of cutting a plurality of semiconductor chip packages into individual semiconductor chip packages for singulation may be further performed. These steps may be performed according to various methods known to those skilled in the art used in the manufacture of semiconductor chip packages.
[0281] The above-mentioned embodiment B is a method of first setting a semiconductor chip and forming a rewiring layer on its electrode pad surface, that is, chip-first mounting. st In addition to the chip-first assembly method described above, the semiconductor chip package of the present invention can also be manufactured using the redistribution layer first assembly (RDL-1 st ) method, the redistribution layer is first installed (RDL-1 st ) method is a method in which a rewiring layer is first provided, and a semiconductor chip is provided on the rewiring layer and sealed in a state in which the electrode pad surface can be electrically connected to the rewiring layer. st The construction method is still RDL-1 st The resin composition of the present invention can realize semiconductor chip packaging with extremely low transmission loss required for next-generation high-speed communication applications.
[0282] By using the resin composition of the present invention that can suppress warping, show good dielectric properties, and maintain good mechanical strength when exposed to a high temperature and high humidity environment, a sealing layer, a rewiring formation layer, etc. are formed, so that no matter whether the semiconductor package is a fan-in (Fan-In) type package or a fan-out (Fan-Out) type package, a semiconductor chip package with very little transmission loss can be achieved. In one embodiment, the semiconductor chip package of the present invention is a fan-out (Fan-Out) type package. The resin composition of the present invention is applicable to both fan-out panel-level package (FOPLP) and fan-out wafer-level package (FOWLP). In one embodiment, the semiconductor package of the present invention is a fan-out panel-level package (FOPLP). In another embodiment, the semiconductor package of the present invention is a fan-out wafer-level package (FOWLP).
[0283] [Printed wiring board] The resin composition of the present invention can be used to produce a printed wiring board. The present invention also provides the printed wiring board. The printed wiring board of the present invention is characterized by comprising an insulating layer formed of a cured product of the resin composition of the present invention.
[0284] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet through a method including the following steps (I) and (II): (I) a step of laminating a resin sheet on an inner substrate so that the resin composition layer of the resin sheet is bonded to the inner substrate; and (II) a step of curing (eg, thermally curing) the resin composition layer to form an insulating layer.
[0285] The "inner substrate" used in step (I) refers to a component that becomes a substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, a thermosetting polyphenylene ether substrate, and the like. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of a substrate is sometimes referred to as an "inner circuit substrate". In addition, an intermediate product that requires further formation of an insulating layer and / or a conductor layer when manufacturing a printed wiring board is also included in the "inner substrate" referred to in the present invention. In the case where the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components can be used.
[0286] The lamination of the inner substrate and the resin sheet can be performed, for example, by heat-pressing the resin sheet to the inner substrate from the support body side. As a component for heat-pressing the resin sheet to the inner substrate (hereinafter also referred to as "heat-pressing component"), for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) etc. can be cited. It should be noted that the heat-pressing component can be directly pressed on the resin sheet, or it can be pressed with an elastic material such as heat-resistant rubber, so that the resin sheet fully conforms to the surface unevenness of the inner substrate.
[0287] The lamination of the inner substrate and the resin sheet can be implemented by vacuum lamination. In the vacuum lamination method, the heating and pressing temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heating and pressing pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heating and pressing time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. Lamination can be preferably implemented under reduced pressure conditions of 26.7hPa or less.
[0288] Lamination can be performed by a commercially available vacuum laminator. Examples of the commercially available vacuum laminator include a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., and a batch vacuum pressure laminator.
[0289] After lamination, the laminated resin sheet can be smoothed by, for example, pressing the heating and pressing member from the support side under normal pressure (atmospheric pressure). The pressing conditions for the smoothing treatment can be the same as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed by a commercially available laminator. It should be noted that the lamination and smoothing treatment can be performed continuously using the above-mentioned commercially available vacuum laminator.
[0290] The support may be removed between step (I) and step (II), or after step (II). It should be noted that when a metal foil is used as the support, the metal foil may be used to form the conductor layer without peeling off the support. In addition, when a metal foil with a supporting substrate is used as the support, the supporting substrate (and the peeling layer) may be peeled off. Thus, the metal foil may be used to form the conductor layer.
[0291] In step (II), the resin composition layer is cured (eg, thermally cured) to form an insulating layer composed of a cured product of the resin composition. The curing conditions of the resin composition layer are not particularly limited, and conditions generally used when forming an insulating layer of a printed wiring board can be used.
[0292] For example, the thermal curing conditions of the resin composition layer vary depending on the type of the resin composition, and in one embodiment, the curing temperature is preferably 120° C. to 250° C., more preferably 150° C. to 240° C., and further preferably 180° C. to 230° C. The curing time may be preferably 5 minutes to 240 minutes, more preferably 10 minutes to 150 minutes, and further preferably 15 minutes to 120 minutes.
[0293] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature of 50°C to 120°C, preferably 60°C to 115°C, more preferably 70°C to 110°C, for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0294] When manufacturing a printed wiring board, the step of (III) opening holes in the insulating layer, the step of (IV) roughening the insulating layer, and the step of (V) forming a conductor layer can be further implemented. These steps (III) to (V) can be implemented according to various methods known to those skilled in the art used in the manufacture of printed wiring boards. It should be noted that when the support body is removed after step (II), the removal of the support body can be implemented between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, the formation of the insulating layer and the conductor layer of steps (I) to (V) can be repeatedly implemented as needed to form a multilayer wiring board.
[0295] In another embodiment, a printed wiring board can be produced using the above-mentioned prepreg. The production method is basically the same as that in the case of using a resin sheet.
[0296] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as through holes and vias in the insulating layer. Step (III) can be carried out using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.
[0297] Step (IV) is a step of roughening the insulating layer. Usually, in step (IV), contamination removal (decontamination) is also performed. The steps and conditions of the roughening treatment are not particularly limited, and the known steps and conditions commonly used when forming the insulating layer of the printed wiring board can be used. For example, the insulating layer can be roughened by swelling treatment using a swelling liquid, roughening treatment using an oxidizing agent, and neutralization treatment using a neutralizing liquid in sequence.
[0298] The swelling liquid used in the roughening treatment is not particularly limited, and examples thereof include alkaline solutions, surfactant solutions, and the like. Alkaline solutions are preferred, and sodium hydroxide solutions and potassium hydroxide solutions are more preferred as the alkaline solutions. Examples of commercially available swelling liquids include "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan Co., Ltd. The swelling treatment using the swelling liquid is not particularly limited, and for example, the insulation layer may be immersed in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of controlling the swelling of the resin of the insulation layer to an appropriate level, it is preferred that the insulation layer be immersed in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.
[0299] As the oxidant used in the roughening treatment, there is no particular limitation, and an alkaline permanganate solution obtained by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide can be cited. The roughening treatment using an oxidant such as an alkaline permanganate solution is preferably carried out by immersing the insulating layer in an oxidant solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. As commercially available oxidants, alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosingsolution Securiganth P" manufactured by Atotech Japan Co., Ltd. can be cited.
[0300] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and examples of commercially available products include "Reduction solution Securiganth P" manufactured by Atotech Japan Ltd.
[0301] The treatment with a neutralizing solution can be performed by immersing the treated surface subjected to the roughening treatment with an oxidizing agent in a neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. From the viewpoint of operability, etc., a method in which the object subjected to the roughening treatment with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes is preferred.
[0302] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. Step (V) can be carried out in the same manner as step (6) described in relation to the method for producing a semiconductor chip package.
[0303] The thickness of the conductor layer varies depending on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, preferably 5 μm to 30 μm.
[0304] The conductor layer can also be formed using metal foil. When a metal foil is used to form the conductor layer, step (V) is preferably implemented between step (I) and step (II). For example, after step (I), the support is removed and a metal foil is laminated on the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil can be implemented by a vacuum lamination method. The lamination conditions can be the same as those described for step (I). Next, step (II) is implemented to form an insulating layer. Then, the metal foil on the insulating layer can be used to form a conductor layer with a desired wiring pattern by conventionally known techniques such as a subtractive method and a modified semi-additive method.
[0305] The metal foil can be produced by a known method such as electrolysis or rolling. Commercially available metal foils include HLP foil and JXUT-III foil manufactured by JX Metals Co., Ltd., and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0306] Alternatively, as described above, when a metal foil or a metal foil with a supporting substrate is used as the support of the resin sheet, the conductor layer can be formed using the metal foil.
[0307] [Semiconductor devices] The semiconductor device of the present invention includes a layer formed of a cured product of the resin composition of the present invention. The semiconductor device of the present invention can be produced using the semiconductor chip package or printed wiring board of the present invention.
[0308] Examples of the semiconductor device include various semiconductor devices used in electrical products (such as computers, mobile phones, digital cameras, and televisions) and vehicles (such as motorcycles, automobiles, trains, ships, and aircraft). Example
[0309] The present invention will be specifically described below by way of examples. The present invention is not limited to these examples. It should be noted that, below, "parts" indicating an amount means "parts by mass" unless otherwise specified.
[0310] <Synthesis Example 1: Synthesis of Resin X1> 112 g of difunctional hydroxy-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl equivalent = 1800 g / eq.), 272 g of anisole as a solvent, and 14 g of isophorone diisocyanate (IPDI) were added to a reaction container, the temperature was raised to 50°C, and the reaction was carried out for about 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends (SABIC SA90-100, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenone tetracarboxylic dianhydride (BTDA) were added to the reactant, and the temperature was raised to 140°C while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reactant was cooled to room temperature. Then, the reactant was filtered with a 100-mesh filter cloth to obtain a resin X1 having a low-polyphenylene ether skeleton (non-volatile component 50% by mass, 25°C viscosity 6.0 Pa·s, weight average molecular weight 280,000, glass transition temperature 0°C).
[0311] <Synthesis Example 2: Synthesis of Resin X2> 60 g of difunctional hydroxyl-terminated polybutadiene ("G-1000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 1400, hydroxyl equivalent = 800 g / eq.), 220 g of anisole as a solvent and 14 g of isophorone diisocyanate (IPDI) were added to a reaction container, the temperature was raised to 50°C, and the reaction was carried out for about 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends (SABIC SA90-100, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenone tetracarboxylic dianhydride (BTDA) were added to the reactant, and the temperature was raised to 140°C while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reactant was cooled to room temperature. Then, the reactant was filtered with a 100-mesh filter cloth to obtain a resin X2 having a low polyphenylene ether skeleton (non-volatile content 50% by mass, 25°C viscosity 2.0 Pa·s, weight average molecular weight 260,000, glass transition temperature 0°C).
[0312] <Synthesis Example 3: Synthesis of Resin X3> 83 g of polycarbonate diol ("C-2015N" manufactured by Kuraray Co., Ltd., number average molecular weight = 2000, hydroxyl equivalent = 1000 g / eq.), 240 g of anisole as a solvent, and 14 g of isophorone diisocyanate (IPDI) were added to a reaction container, the temperature was raised to 50°C, and the reaction was carried out for about 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends (SABIC SA90-100, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenone tetracarboxylic dianhydride (BTDA) were added to the reactant, and the temperature was raised to 140°C while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reactants were cooled to room temperature. Then, the reactants were filtered with a 100-mesh filter cloth to obtain a resin X3 having a low-polyphenylene ether skeleton (non-volatile content 50% by mass, 25°C viscosity 4.0 Pa·s, weight average molecular weight 254,000, glass transition temperature -4°C).
[0313] <Synthesis Example 4: Synthesis of Resin X'1> 69 g of difunctional hydroxy-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl equivalent = 1800 g / eq.), 40 g of aromatic hydrocarbon mixed solvent ("Ipzole 150" manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin laurate were added to a reaction container and mixed to uniformly dissolve. After becoming uniform, the temperature was raised to 60° C., and 8 g of isophorone diisocyanate ("IPDI" manufactured by Evonik Degussa Japan Co., Ltd., isocyanate equivalent = 113 g / eq.) was added while stirring, and the reaction was carried out for about 3 hours. Next, 23 g of cresol novolac resin ("KA-1160" manufactured by DIC Corporation, hydroxyl equivalent = 117 g / eq.) and 60 g of ethyl diglycol acetate (manufactured by Daicel Corporation) were added to the reactants, and the temperature was raised to 150°C while stirring, and the reaction was carried out for about 10 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reaction product was cooled to room temperature. Then, the reaction product was filtered with a 100-mesh filter cloth to obtain resin X'1 (phenolic hydroxyl-containing butadiene resin: non-volatile content 50% by mass, glass transition temperature -4°C).
[0314] <Synthesis Example 5: Synthesis of Maleimide A> A MEK solution (non-volatile content 70% by mass) of maleimide A (n=1.47, Mw / Mn=1.81) represented by the following formula synthesized by the method described in Synthesis Example 1 of Japan Invention Association Publication No. 2020-500211 was obtained and blended into the resin composition in Example 9 described below.
[0315] [Chemical formula 24]
[0316] [Examples 1 to 12, Comparative Examples 1 to 3] (1) Preparation of resin composition Each component was weighed according to the blending composition described in Table 1, and 15 parts of MEK was further mixed and uniformly dispersed using a high-speed rotary mixer to obtain a resin composition (resin varnish).
[0317] (2) Manufacture of resin sheets As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) having a release layer was prepared. The obtained resin varnish was evenly coated on the release layer of the support so that the thickness of the resin composition layer after drying was 50 μm. Then, the resin composition was dried at 80° C. to 120° C. (average 100° C.) for 4 minutes to obtain a resin sheet having a layer structure of resin composition layer / support.
[0318] <Determination of bolt tension strength> 1. Lamination of resin sheets For the resin sheets made in the embodiments and comparative examples, a batch vacuum pressurized laminator (Nikko-Materials 2-stage stacking laminator "CVP700") is used to laminate the resin composition layer on a single side of a 12-inch silicon wafer (thickness 775 μm). The lamination is implemented by pressing at a temperature of 100 ° C and a pressure of 0.74 MPa for 30 seconds after reducing the pressure for 30 seconds to make the air pressure less than 3 hPa. After AL5 is peeled off, it is put into an oven at 200 ° C and heated for 90 minutes to cure the resin composition layer. In this way, an "evaluation wafer A" having a cured layer of a resin composition on a 12-inch silicon wafer is obtained. Evaluation wafer A is prepared for each resin composition.
[0319] 2. Bolt traction test (1) Test conditions The load value (kgf / cm2) during peeling was evaluated using a stud pull tester (ROMULUS, manufactured by Quad Group Inc.) according to the following procedure. 2 ). That is, on the cured layer of the resin composition of the evaluation wafer A, an aluminum bolt pin with epoxy adhesive (adhesive surface diameter 2.7 mmφ; P / N 901106) was fixed with a back plate on the opposite side and heated in an oven at 150°C for 1 hour to bond the bolt pin to the cured layer. Then, in the above-mentioned bolt pulling tester, the stud pin was pulled at a speed of 2 kgf / sec in a direction perpendicular to the main surface of the evaluation wafer, and the load value (kgf / cm 2 ) The test was performed on all the evaluation wafers A prepared for each resin composition (N=5).
[0320] <Warping Evaluation> Using a batch vacuum pressurized laminator (Nikko-Materials company 2-stage stacking laminator "CVP700"), on a 12-inch silicon wafer (thickness 775μm), the resin sheet made in the embodiment and the comparative example is laminated on the entire single side of the silicon wafer in a manner that the resin composition layer is bonded to the silicon wafer. Peel off the support, and further laminate the resin sheet in the same manner on the surface of the exposed resin composition layer, and peel off the support. Thus, a 2-layer resin composition layer (total thickness 100μm) is formed on a single side of a 12-inch silicon wafer. It should be noted that lamination (lamination treatment and smoothing treatment) is implemented under the same conditions as above 1. The obtained laminated body was heated in an oven at 200° C. for 90 minutes to cure the resin composition layer to form an insulating layer. Thus, an evaluation wafer B including a silicon wafer and a cured product of the resin composition layer was obtained. The warpage of the evaluation wafer B was measured using a shadow moire measuring device ("Thermoire AXP" manufactured by Akorometrix). The measurement was performed in accordance with JEITAEDX-7311-24 of the Electronics and Information Technology Industry Association standard. Specifically, the fitting plane obtained by the least squares method for all data on the evaluation substrate surface of the measurement area was used as the reference plane, and the difference between the minimum and maximum values in the vertical direction from the reference plane was calculated as the warpage. The measured values were evaluated according to the following benchmarks. ○: The warpage amount is 0 μm or more and less than 1000 μm △: Warpage is 1000 μm or more and less than 1500 μm ×: Warpage amount is 1500 μm or more
[0321] <Measurement of dielectric loss tangent> The resin sheets obtained in the examples and comparative examples were heated at 200°C for 90 minutes to thermally cure the resin composition layer. The support was then peeled off to obtain a cured product of the resin composition layer. The cured product was cut into pieces with a width of 2 mm and a length of 80 mm to prepare test pieces for evaluation. For each test piece for evaluation, the dielectric loss tangent (Df value) was measured by the cavity perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. using "HP8362B" manufactured by Agilent Technologies. The measurement was performed on three test pieces, and the average value was calculated. The average value obtained was evaluated according to the following criteria. ×: Dielectric loss tangent is 0.004 or more △: Dielectric loss tangent exceeds 0.0035 and is less than 0.004 ○: Dielectric loss tangent is less than 0.0035
[0322] <Evaluation of breaking strength> The resin sheets obtained in Examples and Comparative Examples were heated at 200° C. for 90 minutes to thermally cure the resin composition layer. Next, the support was peeled off to obtain a cured product of the resin composition layer. From the cured product, a cured product that was placed in a HAST environment (130° C., 85% RH) for 100 hours and a cured product that was not subjected to this operation were prepared, and a tensile test was performed using a Tensilon universal testing machine ("RTC-1250A" manufactured by Orientec Co., Ltd.) according to Japanese Industrial Standards (JIS K7127) to measure the breaking strength (%) at 23° C. The reduction rate of the breaking strength before and after HAST was evaluated according to the following criteria. ×: Reduction rate exceeds 10% △: The reduction rate is more than 7% and less than 10% ○: Reduction rate is less than 7%
[0323] Table 1 shows the results of Examples 1 to 12 and Comparative Examples 1 to 3.
[0324] [Table 1]
[0325] In addition, the details of each component described in Table 1 are as follows. <Thermosetting resin> 828EL: Bisphenol A epoxy resin, functional group equivalent weight about 180 g / eq, manufactured by Mitsubishi Chemical Corporation HP-6000L: Naphthyl ether type epoxy resin, functional group equivalent weight about 213g / eq, manufactured by DIC Corporation ·YX4000H: Biphenyl type epoxy resin, functional group equivalent 190g / eq, manufactured by Mitsubishi Chemical Corporation <Curing agent> KA-1160: Phenolic curing agent, cresol novolac resin, functional group equivalent 117g / eq, manufactured by DIC Corporation HPC-8000-65T: Active ester curing agent, functional group equivalent 223 g / eq, toluene solution with non-volatile content 65% by mass, manufactured by DIC Corporation V-03: Carbodiimide curing agent, functional group equivalent 216 g / eq, toluene solution containing 50% by mass of nonvolatile matter, manufactured by Nisshinbo Chemical Co., Ltd. <Resin X> Resin X1 to X3: Resins X1 to X3 synthesized in Synthesis Examples 1 to 3, anisole solution containing 50% by mass of nonvolatile components <Resin X'> Resin X'1: Resin X'1 synthesized in Synthesis Example 4, a solution containing 50% by mass of nonvolatile components YX7553BH30: phenoxy resin, 1:1 mixed solution of MEK solution with 30% by mass of nonvolatile components and cyclohexanone, manufactured by Mitsubishi Chemical Corporation <Curing accelerator> ·1B2PZ: Imidazole derivative, manufactured by Shikoku Chemical Industry Co., Ltd. DMAP: 4-dimethylaminopyridine <Maleimide resin> ·BMI-689: Maleimide compound, manufactured by Designer Molecules Inc. ·MIR-3000-70MT: Biphenyl aralkyl novolac type maleimide compound, a mixed solution of MEK solution with a non-volatile content of 70% and toluene, manufactured by Nippon Kayaku Co., Ltd. ·BMI-1500: Maleimide compound, manufactured by Design Molecular Co., Ltd. <Inorganic filler> SO-C2: Spherical silica surface-treated with an amino-based silane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, specific surface area 5.8 m 2 / g, made by Yaduma
Claims
1. A resin composition comprising the following components: Thermosetting resin, Inorganic fillers, and A resin X containing an oligophenylene ether skeleton having a glass transition temperature of 25°C or less, The bolt pull-off strength of the cured product of the resin composition is 600 kgf / cm 2 above.
2. The resin composition according to claim 1, wherein When the resin component in the resin composition is 100 mass %, the content of the resin X is 10 mass % or more and less than 60 mass %.
3. The resin composition according to claim 1, wherein When the nonvolatile component in the resin composition is 100% by mass, the content of the inorganic filler is 50% by mass or more.
4. The resin composition according to claim 1, wherein The resin X contains one or more structural units selected from the group consisting of a polyolefin structural unit, a polycarbonate structural unit, a polyether structural unit, a polyester structural unit, a poly(meth)acrylic acid structural unit, and a polysiloxane structural unit.
5. The resin composition according to claim 1, wherein The resin X contains a cyclic imide structure. The resin composition according to claim 1 , which is used for sealing a semiconductor. The resin composition according to claim 1 , which is used for an insulating layer of a circuit board.
8. A cured product of the resin composition according to any one of claims 1 to 7.
9. A resin sheet, wherein: A layer comprising a support and the resin composition according to any one of claims 1 to 7 provided on the support.
10. The resin sheet according to claim 9, wherein The support is a thermoplastic resin film or a metal foil.
11. A semiconductor chip package, wherein: The invention comprises a sealing layer formed of a cured product of the resin composition according to any one of claims 1 to 7.
12. A circuit substrate, wherein: An insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 7.
13. A semiconductor device, wherein: A semiconductor chip package comprising the semiconductor chip package according to claim 11.
14. A semiconductor device, wherein: A circuit substrate comprising the circuit substrate according to claim 12.
